Modified sulfide solid electrolyte, manufacturing method thereof, electrode composite material and lithium ion battery

By adhering specific compounds on the surface of the sulfide solid electrolyte, the modified sulfide solid electrolyte is solved, and the problems of high paste viscosity and poor coating adaptability in lithium-ion batteries are significantly improved.

CN119547157APending Publication Date: 2025-02-28IDEMITSU KOSAN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380053405.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-07-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the manufacturing process, the solid electrolyte used in the existing lithium-ion battery has problems such that the viscosity of the paste becomes higher and the coating adaptability is reduced, resulting in a degradation of battery performance.

Method used

By attaching a specific compound (such as a compound with a formyl group, acetyl group, a halogen-containing group, etc.) to the surface of a sulfide solid electrolyte with a larger specific surface area, a modified sulfide solid electrolyte is formed, thereby improving its coating adaptability in the paste.

Benefits of technology

Excellent coating adaptability of paste is achieved, and the battery performance of lithium-ion batteries is significantly improved, including improving the density and circulation characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239021970000081
    Figure BDA0005239021970000081
  • Figure BDA0005239021970000082
    Figure BDA0005239021970000082
  • Figure BDA0005239021970000091
    Figure BDA0005239021970000091
Patent Text Reader

Abstract

Provided is a modified sulfide solid electrolyte which is capable of effectively exhibiting excellent battery performance even when applied as a paste even if the sulfide solid electrolyte has a large specific surface area, the modified sulfide solid electrolyte comprising: a sulfide solid electrolyte which has a BET specific surface area of 10 m2 / g or more and contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms; at least one compound selected from among predetermined compounds (1)-(6), a method for producing the modified sulfide solid electrolyte, and an electrode composite material and a lithium ion battery using the modified sulfide solid electrolyte are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified sulfide solid electrolyte and a preparation method thereof, an electrode composite material and a lithium ion battery. Background Art

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras and mobile phones, the development of batteries used as their power sources has also attracted attention. Among them, lithium-ion batteries have attracted attention due to their high energy density.

[0003] In the past, an electrolyte containing a flammable organic solvent was used in a battery for such a purpose, and therefore, a safety device for suppressing the temperature rise during a short circuit, a structure for preventing a short circuit, and improvements in materials were required. In contrast, by changing the electrolyte to a solid electrolyte and making the battery fully solid, a flammable organic solvent is not used in the battery, and the safety device is simplified, and the manufacturing cost and productivity are excellent, so a battery in which the electrolyte is replaced by a solid electrolyte layer is developed.

[0004] As a solid electrolyte used in the solid electrolyte layer, sulfide solid electrolytes are known in the past. For sulfide solid electrolytes, it is first desired to improve the ion conductivity, and further, it is also required to improve the battery performance when used in lithium ion batteries. As methods for improving these performances, for example, a technique for coating the surface of a solid electrolyte, a technique for preparing a composition containing a solid electrolyte and an organic compound, etc. have been studied.

[0005] For example, in Patent Document 1, in order to improve ion conductivity, a method for manufacturing a composite solid electrolyte in which a specified halogenated hydrocarbon compound is used as a coating material to coat the surface of a sulfide solid electrolyte is proposed. Patent Document 2 discloses a solid electrolyte composition in which a compound having a C=O bond and a compound having an S=O bond are used to form a coating on the surface of the solid electrolyte in order to improve the affinity between the active material used in the negative electrode, positive electrode, etc. when manufacturing a lithium-ion battery and the sulfide solid electrolyte, thereby improving the cycle characteristics. In Patent Document 3, as a solid electrolyte composition capable of manufacturing an all-solid secondary battery showing excellent battery capacity, a solid electrolyte composition containing a dispersion medium such as a ketone compound and an alcohol compound is disclosed.

[0006] In addition, for example, in Patent Document 4, in order to achieve good cycle characteristics, a solid electrolyte composition containing a fluorine-containing compound is disclosed, the fluorine-containing compound containing fluorine atoms and P=O or C=O. Patent Document 5 discloses the following technology: as an all-solid secondary battery that suppresses the growth of lithium dendrites, is not prone to short circuits, and can suppress the reduction of battery voltage at a high level, a solid electrolyte composition containing an inorganic solid electrolyte and an organic compound having a non-ionic monovalent halogen atom other than fluorine is used as a solid electrolyte layer.

[0007] Furthermore, for example, Patent Document 6 discloses that in a sulfide solid electrolyte containing lithium, phosphorus, and sulfur and also containing an ester compound of carboxylic acid and alcohol, the ester compound is bonded to or adsorbed on the surface of the conductive sulfide to improve the cycle characteristics of a solid battery, and the sulfide solid electrolyte is obtained by a production method having a step of wet-grinding a slurry containing a lithium ion conductive sulfide, an organic solvent, and the ester compound. In addition, Patent Document 7 discloses a technology for improving ion conductivity by coating a sulfide solid electrolyte with a predetermined organic compound having a halogen element as a functional group as a coating agent, and Patent Document 8 discloses a technology for improving ion conductivity and formability by containing a phosphorus compound such as a phosphate ester.

[0008] As described above, in recent years, with the goal of practical application of lithium-ion batteries, there have been various requirements for improving not only the ion conductivity of the sulfide solid electrolyte itself, but also other performances, such as the performance when the solid electrolyte is applied to lithium-ion batteries. In order to meet such requirements, research is currently underway on technologies for coating the surface of the solid electrolyte and technologies for preparing a composition containing a solid electrolyte and an organic compound.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2020-87633

[0012] Patent Document 2: Japanese Patent Application Publication No. 2017-147173

[0013] Patent Document 3: International Publication No. 2019 / 151373

[0014] Patent Document 4: Japanese Patent Application Publication No. 2017-157300

[0015] Patent Document 5: Japanese Patent Application Publication No. 2019-067523

[0016] Patent Document 6: International Publication No. 2020 / 203231

[0017] Patent Document 7: Japanese Patent Application Publication No. 2020-087633

[0018] Patent Document 8: Japanese Patent Application Publication No. 2020-166994 Summary of the invention

[0019] Technical problem to be solved by the invention

[0020] The present invention has been made in view of such actual conditions, and its object is to provide a modified sulfide solid electrolyte having excellent coating adaptability when applied as a paste and capable of effectively exhibiting excellent battery performance, and a method for producing the same, as well as an electrode composite material and a lithium ion battery exhibiting excellent battery performance.

[0021] Solutions for solving the above technical problems

[0022] The modified sulfide solid electrolyte of the present invention is:

[0023] A modified sulfide solid electrolyte, comprising: a sulfide solid electrolyte having a BET specific surface area of ​​10 m 2 / g or more and containing a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom; at least one compound selected from the following compounds (1) to (6).

[0024] Compound (1) a compound having a formyl group (CH(=O)-);

[0025] Compound (2) a compound having one or more acetyl groups (CH3C(=O)-);

[0026] Compound (3) a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom or a bromine atom) and an organic group;

[0027] Compound (4) a thiol compound;

[0028] Compound (5) a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom);

[0029] Compound (6) is a boron compound containing no metal.

[0030] The method for preparing the modified sulfide solid electrolyte of the present invention is:

[0031] A method for manufacturing a modified sulfide solid electrolyte comprising: preparing a sulfide solid electrolyte having a BET specific surface area of ​​10 m 2 / g or more of a sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, at least one compound selected from the following compounds (1) to (6), and an organic solvent; and

[0032] The organic solvent is removed.

[0033] Compound (1) a compound having a formyl group (CH(=O)-);

[0034] Compound (2) a compound having one or more acetyl groups (CH3C(=O)-);

[0035] Compound (3) a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom, a chlorine atom, a bromine atom or an iodine atom) and an organic group;

[0036] Compound (4) a thiol compound;

[0037] Compound (5) a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom);

[0038] Compound (6) is a boron compound containing no metal.

[0039] The electrode composite material of the present invention is:

[0040] An electrode composite material comprises the modified sulfide solid electrolyte of the present invention and an electrode active material.

[0041] Furthermore, the lithium ion battery of the present invention is,

[0042] A lithium ion battery comprises at least one of the modified sulfide solid electrolyte of the present invention and the electrode composite material of the present invention.

[0043] Effects of the Invention

[0044] The present invention can provide a modified sulfide solid electrolyte having excellent coating suitability when applied as a paste and capable of effectively exhibiting excellent battery performance, and a method for producing the same, and can also provide an electrode composite material and a lithium ion battery exhibiting excellent battery performance. DETAILED DESCRIPTION

[0045] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limits of the numerical ranges of "above", "below", and "to" are numerical values ​​that can be combined arbitrarily, and the numerical values ​​of the embodiments can also be used as the upper and lower limits.

[0046] (Discovery made by the inventors to complete the present invention)

[0047] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and, as a result, have found the following matters and have completed the present invention.

[0048] Conventionally, there is a technique of coating or containing a certain compound on the surface of a sulfide solid electrolyte, as in Patent Documents 1 to 8. The problem of the techniques in Patent Documents 1 to 8 is to improve the battery performance such as improving the cycle characteristics by improving the affinity between the active material used in the negative electrode, positive electrode, etc. and the sulfide solid electrolyte when manufacturing a lithium ion battery by using the technique.

[0049] However, in the manufacturing process of lithium-ion batteries (also called "all-solid batteries"), a paste mixed with a solid electrolyte, other specified components and a solvent is prepared and applied to form a diaphragm layer and an electrode composite material layer. In order to improve the performance of these layers, it is necessary to increase the density of the solid electrolyte constituting these layers. For the increase in this density, it is effective to use a solid electrolyte with a large specific surface area.

[0050] There is a requirement to use a solid electrolyte with a large specific surface area as the solid electrolyte, but if the specific surface area of ​​the solid electrolyte is large, there will be manufacturing problems such as increased viscosity of the paste and significantly reduced coating adaptability. On the other hand, although the coating adaptability of the paste can be improved by reducing the viscosity of the paste by using a large amount of solvent, there will be problems such as a longer drying time or a decrease in the density of the solid electrolyte constituting the layer, which leads to reduced battery performance. Therefore, the coating adaptability of the paste is in a contradictory relationship with obtaining higher battery performance. Like this, a solid electrolyte with a large specific surface area of ​​10m 2 As described above, when a sulfide solid electrolyte with a concentration of 100 μg or more is made into a paste, the viscosity becomes high, which not only significantly reduces the coating suitability, but also requires a large amount of solvent to reduce the viscosity of the paste, thereby prolonging the drying time and significantly reducing the battery performance due to the reduction in density.

[0051] Many methods have been studied to improve ion conductivity and battery performance as technical issues, such as Patent Documents 1 to 8. However, as lithium-ion batteries are rapidly becoming practical, no research has been conducted on methods to improve performance in the manufacturing process, such as paste coating suitability, with an eye toward mass production.

[0052] The present inventors have continued to conduct intensive research based on the techniques disclosed in Patent Documents 1 to 8 for coating a certain compound on the surface of a sulfide solid electrolyte and have found that even a sulfide solid electrolyte with a large specific surface area of ​​10 m 2 / g or more sulfide solid electrolyte, by attaching a predetermined compound to its surface, can also be made into a sulfide solid electrolyte that has excellent coating adaptability when applied as a paste and can effectively demonstrate excellent battery performance. By attaching the predetermined compound used in the present invention to the surface of the sulfide solid electrolyte, even if the specific surface area is large and is 10m 2 / g or more, even a sulfide solid electrolyte can obtain an effect of excellent coating suitability when applied as a paste, which is a surprising phenomenon that has never been recognized so far.

[0053] In this specification, "solid electrolyte" refers to an electrolyte that remains solid at 25° C. in a nitrogen atmosphere. The "sulfide solid electrolyte" obtained by the production method of this embodiment is a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and having ion conductivity caused by lithium atoms.

[0054] The "sulfide solid electrolyte" includes both crystalline sulfide solid electrolytes and amorphous sulfide solid electrolytes having a crystal structure. In this specification, the crystalline sulfide solid electrolyte refers to a solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in a powder X-ray diffraction (XRD) measurement, and is a material that is independent of whether or not there is a peak derived from a raw material of the solid electrolyte. That is, the crystalline sulfide solid electrolyte includes a crystal structure derived from a solid electrolyte, and a part of it may be a crystal structure derived from the solid electrolyte, or all of it may be a crystal structure derived from the solid electrolyte. In addition, as long as the crystalline sulfide solid electrolyte has the above-mentioned X-ray diffraction pattern, it may also include an amorphous sulfide solid electrolyte (also referred to as a "glass component") in a part thereof. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating an amorphous solid electrolyte (glass component) to a crystallization temperature or above.

[0055] In addition, in this specification, an amorphous sulfide solid electrolyte (glass component) means that in powder X-ray diffraction (XRD) measurement, the X-ray diffraction pattern is a halo pattern in which substantially no peaks other than peaks derived from the material are observed, regardless of the presence or absence of peaks derived from the raw materials of the solid electrolyte.

[0056] In the present embodiment, the above distinction between crystallinity and amorphousness is also applicable to both the sulfide solid electrolyte and the modified sulfide solid electrolyte.

[0057] (Various Aspects of the Present Embodiment)

[0058] The modified sulfide solid electrolyte of the first embodiment of the present invention is:

[0059] A modified sulfide solid electrolyte, comprising: a sulfide solid electrolyte having a BET specific surface area of ​​10 m 2 / g or more and containing a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom; at least one compound selected from the following compounds (1) to (6).

[0060] Compound (1) a compound having a formyl group (CH(=O)-);

[0061] Compound (2) a compound having one or more acetyl groups (CH3C(=O)-);

[0062] Compound (3) a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom or a bromine atom) and an organic group;

[0063] Compound (4) a thiol compound;

[0064] Compound (5) a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom);

[0065] Compound (6) is a boron compound containing no metal.

[0066] As the sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, a sulfide solid electrolyte obtained by a conventional method, for example, using lithium sulfide, phosphorus pentasulfide, lithium halide, monomeric halogen, etc. as raw materials can be typically exemplified. That is, the modified sulfide solid electrolyte of the present embodiment includes a sulfide solid electrolyte having a BET specific surface area of ​​10 m2 obtained by a conventional method. 2 / g or more, and a sulfide solid electrolyte having a large specific surface area and the specific compound of the above compounds (1) to (6).

[0067] In the past, the BET specific surface area was relatively large, only 10m 2 In a sulfide solid electrolyte having a content of more than 100 g, the coating performance of the paste containing the required content to ensure the density of the solid electrolyte in the layer in order to exhibit the specified battery performance is significantly reduced, and it is extremely difficult to effectively form the positive electrode, negative electrode, and electrolyte layer. The sulfide solid electrolyte of the present embodiment contains a conventional sulfide solid electrolyte and specific compounds (1) to (6), and has a significantly improved coating suitability, that is, it is "modified" and should be called a "modified sulfide solid electrolyte".

[0068] The above-mentioned specific compounds (1) to (6) used in the modified sulfide solid electrolyte of the present embodiment are common in that they are all compounds containing heteroatoms such as oxygen atoms, halogen atoms, sulfur atoms, phosphorus atoms, and boron atoms. As the modified sulfide solid electrolyte of the present embodiment, among the compounds containing heteroatoms, it is necessary to use compounds having specific structures such as the above-mentioned compounds (1) to (6). By using such compounds, the coating adaptability when applied as a paste is excellent and the effect of being able to effectively show excellent battery performance is achieved.

[0069] In the modified sulfide solid electrolyte of the present embodiment, it has not been determined how the above compounds (1) to (6) are contained, but it is presumed that these compounds adhere to the surface of the sulfide solid electrolyte while maintaining their structures.

[0070] The examples confirmed that the sulfide solid electrolyte containing the above compounds (1) to (6) has a lower oil absorption than the sulfide solid electrolyte not containing the above compounds (1) to (6). It is reasonable to assume that the reduction in oil absorption is caused by the above compounds (1) to (6) adhering to the surface of the sulfide solid electrolyte and blocking at least a portion of the pores possessed by the sulfide solid electrolyte. It is generally known that in order to improve coating adaptability, the oil absorption is also related to the specific surface area. It can be inferred that by allowing the above compounds (1) to (6) to adhere to the surface of the sulfide solid electrolyte, the oil absorption is reduced and the coating adaptability is improved.

[0071] It is not clear in what form the above compounds (1) to (6) adhere to the surface of the sulfide solid electrolyte, that is, whether they adhere physically or chemically. However, since heteroatoms such as oxygen atoms have the property of easily bonding with lithium atoms, halogen atoms, etc., it is highly likely that the heteroatoms contained in the above compounds (1) to (6) are bonded with lithium atoms, halogen atoms, etc. constituting the sulfide solid electrolyte and adhere to the surface, that is, chemically adhere. Considering the above speculation, it is believed that the oil absorption is reduced and the coating suitability is improved regardless of whether it is chemical adhesion or physical adhesion.

[0072] In the modified sulfide solid electrolyte of the present embodiment, it is considered that the oil absorption is easily reduced as long as the above compounds (1) to (6) are attached to the surface, regardless of which of the above-mentioned attachments are used, and as a result, the coating suitability is improved, and the battery performance can be improved.

[0073] The modified sulfide solid electrolyte of the second embodiment of the present invention is, in the above-mentioned first embodiment,

[0074] The compound (1) is a compound represented by the following general formula (1).

[0075] [Chemistry 1]

[0076]

[0077] (In the general formula (1), R 11 and R 12 Each independently represents an organic group or a single bond, X 11 represents an oxygen atom, a sulfur atom, a group represented by the general formula (1a) or a single bond, n 11 represents 0 or 1. In the general formula (1a), R 11a and R 12a Each independently represents an organic group. )

[0078] As described above, in the modified sulfide solid electrolyte of the present embodiment, any of compounds (1) to (6) can be used without particular limitation, and excellent coating suitability can be obtained. Compound (1) is a compound having a formyl group (CH(=O)-), which can be said to be a compound having a formyl group at at least one end of the compound. Among such compounds, by using a compound having 1 or 2 formyl groups (CH(=O)-) represented by the above general formula (1) as compound (1), the oil absorption is reduced, excellent coating suitability is easily obtained, and excellent battery performance can be obtained more effectively.

[0079] It is believed that the attachment of the above-mentioned compound (1) is preferably moderate attachment. This is because if it is moderate attachment, the coating adaptability is improved by the effect of reducing the oil absorption, thereby improving the battery performance. On the other hand, it is possible to suppress the reduction of ionic conductivity and suppress the reduction of the effect of improving battery performance brought about by the improvement of coating adaptability. Therefore, as compound (1), it is preferably a compound having a specific structure as represented by the above-mentioned general formula (1). This is because it is believed that a moderate chemical or physical attachment state can be obtained by moderate steric hindrance.

[0080] The modified sulfide solid electrolyte of the third aspect of the present embodiment is, in the first or second aspect,

[0081] The compound (2) is a compound represented by the following general formula (2).

[0082] [Chemistry 2]

[0083]

[0084] (In general formula (2), R 21 and R 22 Each independently represents an organic group or a single bond, X 21 represents an oxygen atom, a sulfur atom or a single bond, n 21 Indicates 0 or 1. )

[0085] Compound (2) is a compound having one or more acetyl groups (CH3C(=O)-), which can be said to be a compound having an acetyl group at at least one terminal of the compound. Among such compounds, by using a compound represented by the above general formula (2) having an acetyl group at at least one terminal as compound (2), the oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0086] Furthermore, it is believed that by using a compound having a specific structure represented by the above general formula (2) as compound (2), a suitable chemical or physical adhesion state can be obtained due to suitable steric hindrance as described above for compound (1). Therefore, the oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0087] A modified sulfide solid electrolyte according to a fourth aspect of the present embodiment is, in any one of the first to third aspects,

[0088] The compound (3) is a compound represented by the following general formula (3).

[0089] [Chemistry 3]

[0090]

[0091] (In general formula (3), R 31 represents an organic group or a single bond, X 31 and X 32 Each independently represents a fluorine atom or a bromine atom. )

[0092] Compound (3) is a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom or a bromine atom) and an organic group, and can be said to be a compound having halogen-containing groups represented by -CH2X (X represents a fluorine atom or a bromine atom) at at least two ends of the organic group. Among such compounds, by using a compound represented by the above general formula (3) having halogen-containing groups at both ends as compound (3), the oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0093] Furthermore, it is considered that by using a compound having a specific structure represented by the above general formula (3) as compound (3), as described for the above compound (1), a moderate chemical or physical attachment state can be obtained due to moderate steric hindrance, thereby reducing the oil absorption, making it easier to obtain excellent coating adaptability, and more effectively obtaining excellent battery performance.

[0094] A modified sulfide solid electrolyte according to a fifth aspect of the present embodiment is, in any one of the first to fourth aspects,

[0095] The compound (4) is at least one compound selected from the group consisting of a compound represented by the following general formula (4-1) and a compound represented by the following general formula (4-2).

[0096] [Chemistry 4]

[0097]

[0098] (In general formula (4-1), R 411 , R 412 and R 413 Each independently represents an organic group or a single bond, X 411 represents a hydrogen atom or a thiol group, n 411 represents an integer from 0 to 3. 411 , R 412 and R 413 At least one of R is an organic group. 421 , R 422 and R 423 Each independently represents an organic group. 421 、n 422 Integer from 0 to 3, n 421 and n 422 Satisfy n 421 +n 422 =3. )

[0099] Compound (4) is a thiol compound, i.e., a compound having a thiol group, wherein by using a compound represented by the above general formula (4) having a thiol group at at least one end (a compound having a thiol group at one end or both ends), the oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be more effectively obtained.

[0100] Furthermore, it is considered that by using a compound having a specific structure represented by the above general formula (4) as compound (4), as described for the above compound (1), a moderate chemical or physical attachment state can be obtained due to moderate steric hindrance, thereby reducing the oil absorption, making it easier to obtain excellent coating adaptability, and more effectively obtaining excellent battery performance.

[0101] A modified sulfide solid electrolyte according to a sixth aspect of the present embodiment is, in any one of the first to fifth aspects,

[0102] The compound (5) is at least one compound selected from the group consisting of a compound represented by the following general formula (5-1), a compound represented by the following general formula (5-2), and a compound represented by the following general formula (5-3).

[0103] [Chemistry 5]

[0104]

[0105] (In general formula (5-1), R 511 , R 512 and R 513 Each independently represents an organic group. 521 , R 522 and R 523 Each independently represents an organic group. 531 , R 532 , R 535 and R 536 R each independently represents an organic group. 533 and R 534 Each independently represents a single bond or an organic group, X 531 represents a single bond or an oxygen atom. In addition, R 533 and R 534 At least one of R is an organic group, 533 With R 534 They can bond to each other to form a fused ring.)

[0106] Compound (5) is a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom), wherein by adopting the metal-free phosphorus compound represented by the above-mentioned general formulas (5-1), (5-2) and (5-3), the oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0107] In addition, it is believed that by using a compound having a specific structure represented by the above general formula (5-1), (5-2) and (5-3) as compound (5), as described for the above compound (1), a moderate chemical or physical adhesion state can be obtained through moderate steric hindrance, thereby reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance.

[0108] A modified sulfide solid electrolyte according to a seventh aspect of the present embodiment is, in any one of the first to sixth aspects,

[0109] The molecular weight of the compound (5) is 3,000 or less.

[0110] When the molecular weight of the compound (5) is 3000 or less, the oil absorption is reduced, and excellent coating suitability is easily obtained, and excellent battery performance can be obtained more effectively.

[0111] The modified sulfide solid electrolyte according to an eighth aspect of the present embodiment is, in any one of the first to seventh aspects,

[0112] The compound (6) is a compound represented by the following general formula (6).

[0113] [Chemistry 6]

[0114]

[0115] (In general formula (6), R 61 , R 62 and R 63 Each independently represents an organic group. )

[0116] Compound (6) is a metal-free boron compound. By using the metal-free boron compound represented by the above general formula (6), the oil absorption is reduced, excellent coating suitability is easily obtained, and excellent battery performance can be obtained more effectively.

[0117] Furthermore, it is considered that by using a compound having a specific structure represented by the above general formula (6) as compound (6), as described for the above compound (1), a moderate chemical or physical attachment state can be obtained due to moderate steric hindrance, thereby reducing the oil absorption, making it easier to obtain excellent coating adaptability, and more effectively obtaining excellent battery performance.

[0118] A ninth modified sulfide solid electrolyte according to the present embodiment is, in any one of the first to eighth embodiments,

[0119] The content of the compound is 0.03 parts by mass or more and 25 parts by mass or less relative to 100 parts by mass of the sulfide solid electrolyte.

[0120] If the content of compounds (1) to (6) is 0.03 parts by mass or more and 25 parts by mass or less relative to 100 parts by mass of the sulfide solid electrolyte, these compounds are appropriately dispersed and attached to the surface of the sulfide solid electrolyte to reduce the oil absorption, and the ion conductivity can be appropriately maintained, so the coating adaptability is easily improved, and excellent battery performance is easily and effectively manifested. Regarding the content of the compound, as long as the amount of the compound used when manufacturing the modified sulfide solid electrolyte is known, the amount used directly becomes the content.

[0121] The method for producing a modified sulfide solid electrolyte according to the tenth aspect of the present embodiment is:

[0122] A method for manufacturing a modified sulfide solid electrolyte comprising: preparing a sulfide solid electrolyte having a BET specific surface area of ​​10 m 2 / g or more of a sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, at least one compound selected from the following compounds (1) to (6), and an organic solvent; and

[0123] The organic solvent is removed.

[0124] Compound (1) a compound having a formyl group (CH(=O)-);

[0125] Compound (2) a compound having one or more acetyl groups (CH3C(=O)-);

[0126] Compound (3) a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom, a chlorine atom, a bromine atom or an iodine atom) and an organic group;

[0127] Compound (4) a thiol compound;

[0128] Compound (5) a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom);

[0129] Compound (6) is a boron compound containing no metal.

[0130] As described above, the modified sulfide solid electrolyte of the present embodiment is not particularly limited in its production method as long as it is a modified sulfide solid electrolyte containing compounds (1) to (6). According to the method for producing a modified sulfide solid electrolyte of the tenth aspect of the present embodiment, compounds (1) to (6) can be compounds that are attached to the surface of the sulfide solid electrolyte and exist, so the coating suitability is excellent, and excellent battery performance can be effectively demonstrated, and it becomes possible to more efficiently produce such a modified sulfide solid electrolyte of the present embodiment.

[0131] By mixing the sulfide solid electrolyte, compounds (1) to (6) and an organic solvent, a solution or slurry mixture can be obtained. However, if the mixture is kept in this state, the modified sulfide solid electrolyte cannot be used. Therefore, the organic solvent may be removed from the solution or slurry.

[0132] The method for producing a modified sulfide solid electrolyte according to an eleventh aspect of the present embodiment is that the organic solvent used in the production method according to the tenth aspect is:

[0133] At least one solvent selected from aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, ether solvents, ester solvents, and nitrile solvents.

[0134] By using the above solvent as the organic solvent, the adhesion of the compounds (1) to (6) to the surface of the sulfide solid electrolyte can be promoted, and the coating suitability can be easily improved.

[0135] An electrode composite material according to a twelfth aspect of the present embodiment includes the modified sulfide solid electrolyte or the like according to any one of the first to ninth aspects and an electrode active material.

[0136] Furthermore, a lithium ion battery according to a thirteenth aspect of the present embodiment includes at least one of the modified sulfide solid electrolyte or the like according to any one of the first to ninth aspects and the electrode active material according to the twelfth aspect.

[0137] As described above, the modified sulfide solid electrolyte of the present embodiment has excellent coating adaptability when applied as a paste, and can effectively demonstrate excellent battery performance. Therefore, the electrode composite material including the modified sulfide solid electrolyte of the present embodiment also has excellent coating adaptability, so that lithium ion batteries can be efficiently manufactured, and the obtained lithium ion batteries have excellent battery performance.

[0138] 〔Modified sulfide solid electrolyte〕

[0139] The modified sulfide solid electrolyte of this embodiment includes: a sulfide solid electrolyte having a BET specific surface area of ​​10 m 2 / g or more and containing a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom; at least one compound selected from the following compounds (1) to (6).

[0140] Compound (1) a compound having a formyl group (CH(=O)-);

[0141] Compound (2) a compound having one or more acetyl groups (CH3C(=O)-);

[0142] Compound (3) a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom or a bromine atom) and an organic group;

[0143] Compound (4) a thiol compound;

[0144] Compound (5) a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom);

[0145] Compound (6) is a boron compound containing no metal.

[0146] Hereinafter, the compounds (1) to (6) contained in the modified sulfide solid electrolyte of the present embodiment will be described.

[0147] (Compound (1))

[0148] The compound (1) used in the modified sulfide solid electrolyte of the present embodiment is a compound having a formyl group (CH(=O)-). As the compound (1), a compound represented by the following general formula (1) can be preferably exemplified. The oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0149] [Chemistry 7]

[0150]

[0151] In the general formula (1), R 11 and R 12 Each independently represents an organic group or a single bond, X 11 represents an oxygen atom, a sulfur atom, a group represented by the general formula (1a) or a single bond, n 11 represents 0 or 1. In the general formula (1a), R 11a and R 12a Each independently represents an organic group.

[0152] R 11 The organic group is a divalent group, R 12 The organic group in n 11 When it is 0, it is a univalent group. 11 When R is 1, it is a divalent group. 11 and R 12 Examples of the organic group include an aliphatic group, an alicyclic group, an aromatic group and a heterocyclic group, and among them, an aliphatic group and an aromatic group are preferred.

[0153] (Aliphatic group)

[0154] The monovalent aliphatic group may, for example, be an alkyl group, an alkenyl group or an alkynyl group. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance, an alkyl group or an alkenyl group is preferred, and an alkyl group is more preferred.

[0155] From the same viewpoint, the carbon number of the monovalent aliphatic group is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, and even more preferably 12 or less.

[0156] As such a monovalent aliphatic group, representative and preferred examples include methyl, ethyl, various propyl, various butyl, various pentyl, various hexyl, various heptyl, various octyl, various nonyl, various decyl, various undecyl, various dodecyl, etc. In the present specification, "various" means including linear, branched and even isomers thereof, for example, if it is various propyl groups, it includes 1-propyl, 2-propyl, 1-methylethyl as linear and branched saturated aliphatic groups having 3 carbon atoms.

[0157] The aliphatic group may be linear or branched, but is preferably linear.

[0158] As the divalent aliphatic group, there can be mentioned groups having a portion obtained by removing one hydrogen atom from the above-mentioned monovalent aliphatic group as a chemical bond, namely, alkanediyl, alkenediyl, and alkynediyl. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, alkanediyl and alkenediyl are preferred, and alkanediyl is more preferred.

[0159] The carbon number of the divalent aliphatic group is preferably 1 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, further preferably 4 or less, and further preferably 3 or less. The rest is the same as the above-mentioned monovalent aliphatic group.

[0160] Furthermore, at least a part of the hydrogen atoms of the aliphatic group may be substituted with a halogen atom, a hydroxyl group, an amino group or the like.

[0161] (Alicyclic Group)

[0162] The monovalent alicyclic group may, for example, be a cycloalkyl group, a cycloalkenyl group or a cycloalkynyl group. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance, a cycloalkyl group or a cycloalkenyl group is preferred, and a cycloalkyl group is more preferred.

[0163] From the same viewpoint, the carbon number of the monovalent alicyclic group is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, and further preferably 12 or less.

[0164] As the alicyclic group, an alicyclic group containing multiple alicyclic rings may also be exemplified, and for example, a group having a chemical bond obtained by removing one hydrogen atom from a basic structure such as: a bonded multi-alicyclic structure such as a bicyclohexyl group; a structure obtained by condensing two or more alicyclic rings such as hexahydronaphthalene, octahydronaphthalene, decahydronaphthalene; a cross-linked cyclic structure such as norbornane, norbornene, adamantane, tricyclodecane, and pinene may also be preferably exemplified. In addition to these, as a basic structure having a double bond in an alicyclic ring, basic structures such as pentalylene and azulene may also be exemplified.

[0165] Furthermore, a structure in which any of the above-mentioned single alicyclic basic structure, multiple alicyclic basic structures, and aromatic ring basic structures described later are bonded or condensed can also be exemplified as a basic structure that can be preferably exemplified.

[0166] One hydrogen atom removed from the above basic structure of the alicyclic group may be a hydrogen atom of the alicyclic ring or a hydrogen atom of a substituent such as an alkyl group (the substituent will be described later) connected to the alicyclic ring.

[0167] The basic structure of the alicyclic group may be an alicyclic group having a heterocyclic ring in which carbon atoms in the alicyclic groups exemplified above are substituted with hetero atoms such as nitrogen atoms, oxygen atoms, sulfur atoms, and phosphorus atoms.

[0168] In addition, the examples of the basic structure of the alicyclic group are representative examples of preferred ones, and the group is not limited to these. For example, a group in which an aromatic group or a heterocyclic group described later is bonded or condensed to an alicyclic group based on the above basic structure may also be included.

[0169] It can also be a structure in which at least a part of the hydrogen atoms in the above-exemplified alicyclic groups or basic structures are replaced by halogen atoms such as fluorine atoms, hydroxyl groups, amino groups, or substituents such as the above-mentioned aliphatic groups. In this case, the aliphatic group is preferably an alkyl group or an alkenyl group, and the carbon number is preferably 1 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, further preferably 6 or less, and further preferably 4 or less.

[0170] The divalent alicyclic group may be a group having a portion obtained by removing one hydrogen atom from the above-mentioned monovalent alicyclic group as a chemical bond. Here, the one hydrogen atom may be a hydrogen atom of an alicyclic ring or a hydrogen atom of a substituent such as an alkyl group connected to the alicyclic ring.

[0171] (Aromatic Group)

[0172] As the monovalent aromatic group, preferably, there can be mentioned a group having a portion obtained by removing one hydrogen atom from the basic structure of: monocyclic aromatic compounds such as benzene, toluene, and styrene; polycyclic aromatic compounds such as biphenyl, diphenylmethane (benzylbenzene), diphenylethane (bibenzyl), methylenetriphenol, and triphenylcyclohexane in which a plurality of aromatic rings are bonded; naphthalene, phenanthrene, anthracene, pyrene, triphenylene, tetracene, and pentacene in which a plurality of aromatic rings are condensed; or polycyclic aromatic compounds such as indene, indacene, acenaphthene, dihydronaphthalene, tetrahydronaphthalene, biphenylene, fluorene, and fluoranthene in which an aromatic ring is condensed with an alicyclic ring; and the like.

[0173] The one hydrogen atom removed from the above basic structure of the aromatic group may be a hydrogen atom of an aromatic ring (including the above condensed polycyclic ring, etc.) or a hydrogen atom of a substituent such as an alkyl group connected to the aromatic ring (including the above condensed polycyclic ring, etc.) (the substituent will be described later). From the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, a group obtained by removing one hydrogen atom from a hydrogen atom of a substituent such as an alkyl group connected to an aromatic ring (including the above condensed polycyclic ring, etc.) is preferred.

[0174] As the aromatic group, among the above, an aromatic group having a monocyclic aromatic compound as a basic structure is preferred, and preferred examples include: a group having a portion obtained by removing one hydrogen atom from an aromatic ring as a chemical bond, such as phenyl, methylphenyl, vinylphenyl, etc.; a group having a portion obtained by removing one hydrogen atom from an alkyl group connected to an aromatic ring as a chemical bond, such as benzyl, phenethyl, phenylpropyl, etc., and more preferred groups having a portion obtained by removing one hydrogen atom from an alkyl group connected to an aromatic ring as a chemical bond, such as benzyl, phenethyl, phenylpropyl, etc.

[0175] The carbon number of the monovalent aromatic group is preferably 6 or more, more preferably 7 or more, and the upper limit is preferably 36 or less, more preferably 24 or less, further preferably 12 or less, and further preferably 10 or less.

[0176] The basic structure of the aromatic group may be a structure having a heterocyclic ring in which the carbon atoms of the aromatic ring (including the above-mentioned condensed polycyclic ring, etc.) in the above-mentioned basic structure are substituted with heteroatoms such as nitrogen atoms, oxygen atoms, sulfur atoms, and phosphorus atoms.

[0177] In addition, the examples of the basic structure of the aromatic group are representative examples only, and are not limited to these. For example, a group in which the above-mentioned alicyclic group or a heterocyclic group described later is bonded or condensed to an aromatic group based on the above-mentioned basic structure may also be included.

[0178] It may also be a structure in which at least a portion of the hydrogen atoms of the aromatic ring (including the above-mentioned condensed polycyclic ring, etc.) in the above-mentioned basic structure is replaced by a halogen atom such as a fluorine atom, a hydroxyl group, an amino group, or a substituent such as the above-mentioned aliphatic group. In this case, the aliphatic group is preferably an alkyl group or an alkenyl group, more preferably an alkyl group, and the carbon number is preferably 1 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, more preferably 6 or less, and further preferably 4 or less.

[0179] When at least a part of the hydrogen atoms of the aromatic ring (including the above-mentioned condensed polycyclic ring and the like) are substituted, as the substituent, an aliphatic group is preferred among the above-mentioned ones, and an alkyl group is more preferred.

[0180] As a divalent aromatic group, a group having a portion obtained by removing one hydrogen atom from the above-mentioned monovalent aromatic group as a chemical bond can be mentioned. Here, the one hydrogen atom may be a hydrogen atom of an aromatic ring or a hydrogen atom of a substituent such as an alkyl group connected to the aromatic ring.

[0181] (Heterocyclic Group)

[0182] Examples of the monovalent heterocyclic group include: saturated or unsaturated monocyclic oxygen-containing heterocyclic compounds such as oxetane, tetrahydrofuran, dihydrofuran, furan, dioxolane, tetrahydropyran, pyran, etc.; saturated or unsaturated monocyclic nitrogen-containing heterocyclic compounds such as pyrrolidine, pyrroline, imidazolidine, imidazoline, imidazole, piperidine, pyridine, piperazine, pyridazine, pyrimidine, pyrazine, triazine, etc.; saturated or unsaturated monocyclic sulfur-containing heterocyclic compounds such as thietane, tetrahydrothiophene, thiophene, thiazane, thiopyran, etc.; Saturated or unsaturated monocyclic oxygen-nitrogen heterocyclic compounds such as tetrahydrooxazole, oxazole, oxadiazole, succinimide, morpholine, oxazine, etc.; saturated or unsaturated monocyclic nitrogen-sulfur heterocyclic compounds such as tetrahydrothiazole, thiazole, thiomorpholine, thiazine, etc.; saturated monocyclic oxygen-sulfur heterocyclic compounds such as oxathiolane, sulfolane, thioxane, dioxothioxane, etc.; monocyclic heterocyclic groups having a chemical bond as a portion obtained by removing one hydrogen atom from the basic structure of monocyclic heterocyclic compounds.

[0183] In addition, for example, there can be mentioned: saturated or unsaturated condensed polycyclic oxygen-containing heterocyclic compounds such as benzofuran, octahydrobenzofuran, benzopyran, benzodioxane, dibenzofuran, xanthene, dibenzodioxin; saturated or unsaturated condensed polycyclic nitrogen-containing heterocyclic compounds such as indoline, indole, indolizine, benzimidazole, azaindole, decahydroquinoline, quinoline, quinoxaline, carbazole, acridine, phenazine, azaadamantane; benzothiophene, benzothiopyran, dodecahydrodibenzothiophene, hexahydrodibenzothiophene, dihydrodibenzothiophene, Saturated or unsaturated fused polycyclic sulfur-containing heterocyclic compounds such as benzothiophene; fused polycyclic oxygen-nitrogen heterocyclic compounds such as furanpyrrole, benzoxazole, benzoxazine, dihydrobenzoxazine and phenoxazine; fused polycyclic nitrogen-containing heterocyclic compounds such as benzothiazole, benzothiadiazole and phenothiazine; bonded polycyclic or fused polycyclic oxygen-sulfur heterocyclic compounds such as phenylthiochromene and phenoxathiol; and polycyclic heterocyclic groups having a chemical bond as a part obtained by removing one hydrogen atom from the basic structure of polycyclic heterocyclic compounds.

[0184] The number of carbon atoms in the monovalent heterocyclic group is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 36 or less, more preferably 24 or less, and further preferably 18 or less.

[0185] As polycyclic heterocyclic compounds, polycyclic fused heterocyclic compounds are mainly exemplified, but only preferred heterocyclic compounds are exemplified representatively, and it is of course possible to include, for example, polycyclic bonded heterocyclic compounds as basic structures. In addition, groups obtained by bonding or condensing, for example, the above-mentioned alicyclic groups and aromatic groups to the above-mentioned heterocyclic groups may also be included.

[0186] One hydrogen atom removed from the above basic structure of the heterocyclic group may be a hydrogen atom of the heterocyclic ring or a hydrogen atom of a substituent such as an alkyl group connected to the heterocyclic ring (the substituent will be described later).

[0187] It may also be a structure in which at least a part of the hydrogen atoms of the heterocyclic group in the above-exemplified basic structure is substituted by a halogen atom such as a fluorine atom, a hydroxyl group, an amino group, or a substituent such as the above-mentioned aliphatic group. In this case, the aliphatic group is preferably an alkyl group or an alkenyl group, more preferably an alkyl group, and the carbon number is preferably 1 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, more preferably 6 or less, and further preferably 4 or less.

[0188] As the divalent heterocyclic group, there can be mentioned a group having a portion obtained by removing one hydrogen atom from the above-mentioned monovalent heterocyclic group as a chemical bond. Here, the one hydrogen atom may be a hydrogen atom of the heterocyclic group or a hydrogen atom of a substituent such as an alkyl group connected to the heterocyclic group.

[0189] X 11 represents an oxygen atom, a sulfur atom, a group represented by the above general formula (1a), or a single bond. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, X 11 An oxygen atom, a group represented by the above-mentioned general formula (1a), or a single bond is preferred.

[0190] In the general formula (1a), R 11a and R 12a Each independently represents an organic group. 11a and R 12a The organic group may be exemplified by the above R 11 and R 12 Among the organic groups described as organic groups, aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups described as monovalent organic groups, aliphatic groups are preferred. In addition, the carbon number of the aliphatic group is preferably 1 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, further preferably 4 or less, and particularly preferably methyl.

[0191] n 11 It represents 0 or 1, and is preferably 0 from the viewpoint of reducing the oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance.

[0192] Regarding R in the above general formula (1): 11 , R 12 , X 11 、n 11 , as a preferred combination, in X 11 When it is a single bond, R11 is a single bond, R 12 is an aliphatic group, n 11 is 0, as R 12 The aliphatic group is preferably an alkyl group, and the carbon number of the alkyl group is as described above.

[0193] As such a compound (1), heptaldehyde (in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 is hexyl), hexanal (in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 is pentyl), undecanal (in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 In addition, compounds having the structure based on this can of course also obtain the same effect.

[0194] In addition, regarding R in the above general formula (1), 11 , R 12 , X 11 、n 11 , as a preferred combination, in X 11 When it is an oxygen atom, R 11 is an aliphatic group, R 12 For aromatic groups, n 11 is 0, as R 11 The aliphatic group is preferably an alkyl group, and the carbon number of the alkyl group is as described above. 12 The aromatic group is preferably an aromatic group with a monocyclic aromatic compound as a basic structure, and more preferably a group in which an aliphatic group (preferably an alkyl group) is connected to the aromatic ring and has a portion obtained by removing one hydrogen atom of the aliphatic group (preferably an alkyl group) as a chemical bond, among which benzyl, phenethyl and phenylpropyl are preferred, and benzyl is more preferred.

[0195] As such a compound (1), benzyloxyacetaldehyde (in the general formula (1), X 11 is an oxygen atom, R 11 is methylene, n 11 is 0, R 12 In addition, compounds having the structure based on this can of course also obtain the same effect.

[0196] In addition, regarding R in the above general formula (1), 11 , R 12 , X11 、n 11 , as a preferred combination, in X 11 In the case of the above general formula (1a), preferably R 11 and R 12 is an aliphatic group, n 11 is 0, about X 11 Preferably, R in the above general formula (1a) 11a and R 12a It is an aliphatic group.

[0197] Here, as R 11 The aliphatic group is preferably an alkyl group, and the carbon number is preferably 1 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, further preferably 4 or less, and particularly preferably methyl. 12 The aliphatic group is preferably an alkyl group, more preferably a branched alkyl group, and among the branched alkyl groups, a tertiary alkyl group (that is, an alkyl group having a structure in which three carbon atoms are linked to one carbon atom) is preferred.

[0198] As R 12 The carbon number of the aliphatic group is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, and further preferably 6 or less. 11a and R 12a The aliphatic group is preferably an alkyl group, and the carbon number is preferably 1 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, further preferably 4 or less, and particularly preferably a methyl group.

[0199] In the modified sulfide solid electrolyte of the present embodiment, the above-mentioned compound (1) can be used alone or in combination of two or more.

[0200] (Compound (2))

[0201] The compound (2) used in the modified sulfide solid electrolyte of the present embodiment is a compound having one or more acetyl groups (CH3C(=O)-). As the compound (2), a compound represented by the following general formula (2) can be preferably exemplified. The oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0202] [Chemistry 8]

[0203]

[0204] In the general formula (2), R 21 and R 22 Each independently represents an organic group or a single bond, X21 represents an oxygen atom, a sulfur atom or a single bond, n 21 Represents 0 or 1.

[0205] R 21 and R 22 The organic group is a divalent organic group, and examples thereof include the above-mentioned R 11 and R 12 The divalent aliphatic group, alicyclic group, aromatic group and heterocyclic group in the organic group described for the organic group are preferably a divalent aliphatic group. 11 and R 12 The same groups are described for the organic groups.

[0206] As R in the above general formula (2) 21 , R 22 , X 21 The preferred combination is preferably R 21 and R 22 One of them is an aliphatic group, the other is a single bond, X 21 is a single bond, as R 21 and R 22 The aliphatic group of any one of , preferably an alkanediyl group.

[0207] The carbon number of the alkanediyl group is 11 and R 12 The content described is based on the carbon number of the divalent aliphatic group, that is, it is preferably 1 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, further preferably 4 or less, and further preferably 3 or less.

[0208] X 21 represents an oxygen atom, a sulfur atom or a single bond. From the viewpoint of reducing oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, X 21 Single bonds are preferred.

[0209] In addition, 21 represents 0 or 1. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, n 21 Preferably 0.

[0210] As such a compound (2), acetylacetone (in the general formula (2), R 21 and X 21 is a single bond, R 22 is methylene, n 21 1). In addition, as such a compound (2), benzyloxyacetone (in the general formula (2), X 21is an oxygen atom, R 21 is methylene, R 22 is benzyl, n 21 In addition, compounds having structures based on these can also obtain the same effects.

[0211] In the modified sulfide solid electrolyte of the present embodiment, the above-mentioned compound (2) can be used alone or in combination of two or more.

[0212] (Compound (3))

[0213] The compound (3) used in the modified sulfide solid electrolyte of the present embodiment is a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom or a bromine atom) and an organic group. As the compound (3), a compound represented by the following general formula (3) can be preferably exemplified. The oil absorption is reduced, excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0214] [Chemistry 9]

[0215]

[0216] In the general formula (3), R 31 represents an organic group or a single bond, X 31 and X 32 Each independently represents a fluorine atom or a bromine atom.

[0217] R 31 The organic group is a divalent organic group, and examples thereof include the above-mentioned R 11 and R 12 Among the divalent aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups described as organic groups, divalent aliphatic groups are preferred.

[0218] As a divalent aliphatic group, 11 and R 12 Similarly, the divalent aliphatic group may include a group having a portion obtained by removing one hydrogen atom from the above-mentioned monovalent aliphatic group as a chemical bond, i.e., an alkanediyl group, an alkenediyl group, and an alkenediyl group. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, an alkanediyl group and an alkenediyl group are preferred, and an alkanediyl group is more preferred.

[0219] The carbon number of the divalent aliphatic group is preferably 1 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, and further preferably 10 or less.

[0220] The aliphatic group may be straight-chain or branched, preferably straight-chain.11 and R 12 The aliphatic groups are the same.

[0221] In addition, about the 31 The divalent alicyclic group, aromatic group and heterocyclic group of the organic group as R 11 and R 12 The same applies to the alicyclic group, aromatic group and heterocyclic group in the organic group.

[0222] R 31 The above-mentioned organic group may be used or a single bond may be used. From the viewpoint of reducing the oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance, the above-mentioned organic group is preferred.

[0223] X 31 and X 32 Each independently represents a fluorine atom or a bromine atom, and X 31 and X 32 They may be the same or different, but are preferably the same from the viewpoint of reducing the oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance.

[0224] Furthermore, it may be a fluorine atom or a bromine atom, but from the same viewpoint as above, a bromine atom is preferred.

[0225] As such a compound (3), 1,3-dibromopropane (in the general formula (3), R 31 is methylene, X 31 and X 32 is a bromine atom), 1,4-dibromobutane (in the general formula (3), R 31 is methylene, X 31 and X 32 is a bromine atom), 1,6-dibromohexane (in the general formula (3), R 31 is 1,4-butanediyl, X 31 and X 32 is a bromine atom), 1,10-dibromodecane (in the general formula (3), R 31 is 1,8-octanediyl, X 31 and X 32 A dihaloalkyl having a bromine atom bonded to the carbon atoms at both ends as a halogen atom is particularly preferred. In addition, a compound having a structure based on this can of course also obtain the same effect.

[0226] In the modified sulfide solid electrolyte of the present embodiment, the above-mentioned compound (3) can be used alone or in combination of two or more.

[0227] (Compound (4))

[0228] The compound (4) used in the modified sulfide solid electrolyte of the present embodiment is a thiol compound. As the compound (4), preferably, compounds represented by the following general formula (4-1) and general formula (4-2) can be mentioned. The oil absorption is reduced, and excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0229] [Chemistry 10]

[0230]

[0231] In the general formula (4-1), R 411 , R 412 and R 413 Each independently represents an organic group or a single bond, X 411 represents a hydrogen atom or a thiol group, n 411 represents an integer from 0 to 3. 411 , R 412 and R 413 At least one of the groups is an organic group.

[0232] In the general formula (4-2), R 421 , R 422 and R 423 Each independently represents an organic group. 421 、n 422 Integer from 0 to 3, n 421 and n 422 Satisfy n 421 +n 422 =3.

[0233] R 411 , R 412 and R 413 The organic group is a divalent organic group, and examples thereof include the above-mentioned R 11 and R 12 Among the divalent aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups described as organic groups, divalent aliphatic groups are preferred.

[0234] From the perspective of reducing oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, R 411 and R 413 The carbon number of the divalent aliphatic group is preferably 1 or more, and the upper limit is preferably 24 or less, more preferably 20 or less, further preferably 16 or less, and further preferably 12 or less.

[0235] From the same point of view, R 412The carbon number of the divalent aliphatic group is preferably 1 or more, and the upper limit is preferably 8 or less, more preferably 6 or less, further preferably 4 or less, and further preferably 2 or less. 42 In the case of (n 411 is an integer of 2 to 3), multiple R 412 They may be the same or different, but are preferably the same.

[0236] The aliphatic group may be straight-chain or branched, preferably straight-chain. 11 and R 12 The aliphatic groups are the same.

[0237] In addition, about the 411 , R 412 and R 413 The divalent alicyclic group, aromatic group and heterocyclic group of the organic group as R 11 and R 12 The same applies to the alicyclic group, aromatic group and heterocyclic group in the organic group.

[0238] R 411 , R 412 and R 413 The above-mentioned single bond may be used, but from the viewpoint of reducing the oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance, it is preferred that at least one of them is the above-mentioned organic group.

[0239] X 411 represents a hydrogen atom or a thiol group, and may be either, but a hydrogen atom is preferred from the viewpoint of reducing oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance. That is, compound (4) may be a monothiol compound having one thiol group, or may be a dithiol compound having two thiol groups, and a monothiol compound is preferred.

[0240] In addition, 411 It represents an integer of 0 to 3, and from the same viewpoint as above, 0 and 1 are preferred, and 0 is more preferred.

[0241] R 421 The organic group is a divalent organic group, and examples thereof include the above-mentioned R 11 and R 12 The divalent aliphatic group, alicyclic group, aromatic group and heterocyclic group in the organic group described for the organic group are preferably a divalent aliphatic group or aromatic group, and more preferably a divalent aromatic group. 11 and R 12 The same groups are described for the organic groups.

[0242] From the perspective of reducing oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, R 421 The carbon number of the divalent aliphatic group is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, and further preferably 4 or less.

[0243] In addition, regarding the general formula (4-2), R 422 and R 423 is a monovalent organic group, and examples of the above R 11 and R 12 Among the organic groups explained for the organic groups, monovalent aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups are preferably monovalent aliphatic groups. 11 and R 12 The same groups are described for the organic groups.

[0244] From the perspective of reducing oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, R 422 and R 423 The number of carbon atoms in the monovalent aliphatic group is preferably 1 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, further preferably 4 or less, and further preferably 2 or less.

[0245] In addition, when there are multiple R 422 or R 423 In the case of (n 421 is an integer of 1 or 2), multiple R 422 or R 423 They may be the same or different, but are preferably the same.

[0246] R 421 , R 422 and R 423 The aliphatic group may be straight chain or branched, preferably straight chain. 11 and R 12 The aliphatic groups are the same.

[0247] In addition, about the 421 , R 422 and R 423 The monovalent or divalent alicyclic group, aromatic group or heterocyclic group of the organic group, as the above R 11 and R 12 The same applies to the alicyclic group, aromatic group and heterocyclic group in the organic group.

[0248] As such a compound (4), a compound represented by the above general formula (4-1) can be preferably exemplified as a representative example: 1-dodecanethiol (in the general formula (4-1), R 411 is a single bond, n 411 is 0, R 413 is 1,12-dodecanediyl, X 411 is a hydrogen atom), 1,10-decanedithiol (in the general formula (4-1), R 411 is a single bond, n 411 is 0, R 413 is 1,10-decanediyl, X 411 In addition, as a compound represented by the above general formula (4-2), 3-mercaptopropyltrimethoxysilane (in the general formula (4-2), R 421 is 1,3-propanediyl, R 423 Methyl, n 421 is 0, n 422 is 3).

[0249] In addition, it is a matter of course that compounds having a structure based on this can also obtain the same effects.

[0250] In the modified sulfide solid electrolyte of the present embodiment, the above-mentioned compound (4) can be used alone or in combination of multiple compounds, and at least one compound selected from the compound represented by the above-mentioned general formula (4-1) and the compound represented by the general formula (4-2) can be used. For example, the compound represented by the above-mentioned general formula (4-1) can be used alone, or two compounds represented by the above-mentioned general formula (4-1) can be used in combination, and the same is true for the compound represented by the above-mentioned general formula (4-2). In addition, for example, the compound represented by the above-mentioned general formula (4-1) can be used alone or in combination with the compound represented by the general formula (4-2) alone or in combination.

[0251] (Compound (5))

[0252] The compound (5) used in the modified sulfide solid electrolyte of the present embodiment is a phosphorus compound containing no metal (wherein the compound does not contain an oxygen atom single-bonded to a phosphorus atom). The compound (5) may be a phosphorus compound containing no metal atom, where the compound does not contain an oxygen atom single-bonded to a phosphorus atom. That is, the compound (5) does not contain a hydrocarbon group bonded to a phosphorus atom via oxygen, for example, a compound in which various organic groups are bonded to a phosphorus atom via an alkoxy group or an ether bond.

[0253] As the compound (5), preferably, there can be mentioned a compound represented by the following general formula (5-1): The oil absorption is reduced, and excellent coating suitability is easily obtained, and excellent battery performance can be obtained more effectively.

[0254] [Chemistry 11]

[0255]

[0256] In the general formula (5-1), R 511 , R 512 and R 513 Each independently represents an organic group.

[0257] R 511 , R 512 and R 513 The organic group is a monovalent organic group, and examples thereof include the above-mentioned R 11 and R 12 Among the organic groups explained for the organic groups, monovalent aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups are preferably monovalent aliphatic groups. 11 and R 12 The same groups are described for the organic groups.

[0258] About R 511 , R 512 and R 513 The carbon number of the monovalent aliphatic group is preferably 1 or more, more preferably 2 or more, and further preferably 3 or more, from the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance. The upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, and further preferably 10 or less.

[0259] The aliphatic group may be straight-chain or branched, preferably straight-chain. 11 and R 12 The aliphatic groups are the same.

[0260] In addition, about the 511 , R 512 and R 513 The monovalent alicyclic group, aromatic group and heterocyclic group of the organic group as R 11 and R 12 The same applies to the alicyclic group, aromatic group and heterocyclic group in the organic group.

[0261] In addition, R 511 , R 512 and R 513It may be an organic group having an oxygen atom, for example, a group having a group selected from the above-mentioned monovalent aliphatic group, alicyclic group, aromatic group, and heterocyclic group via an oxygen atom. In this case, as a monovalent organic group having a group via an oxygen atom, a group having an oxygen atom and an aliphatic group is preferred.

[0262] As such a compound (5) represented by the general formula (5-1), tri-n-octylphosphine oxide (in the general formula (5-1), R 511 , R 512 and R 513 In addition, compounds having the structure based on this can also obtain the same effect.

[0263] As the compound (5), preferably, a compound represented by the following general formula (5-2) can be mentioned.

[0264] [Chemistry 12]

[0265]

[0266] In the general formula (5-2), R 521 , R 522 and R 523 Each independently represents an organic group.

[0267] R 511 , R 512 and R 513 The organic group is a monovalent organic group, and examples thereof include the above-mentioned R 11 and R 12 Among the organic groups explained with reference to the organic group of , monovalent aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups, monovalent aliphatic groups and aromatic groups are preferred. 11 and R 12 The same groups are described for the organic groups.

[0268] About R 521 , R 522 and R 523 The carbon number of the monovalent aliphatic group is preferably 1 or more, more preferably 2 or more, and further preferably 3 or more, from the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance. The upper limit is preferably 20 or less, more preferably 16 or less, further preferably 12 or less, and further preferably 10 or less.

[0269] The aliphatic group may be straight-chain or branched, preferably straight-chain. 11 and R 12The aliphatic groups are the same.

[0270] As R 521 , R 522 and R 523 The monovalent aromatic group of 11 and R 12 Among the aromatic groups explained as aromatic groups, the aromatic groups having a monocyclic aromatic compound as a basic structure are preferably phenyl groups.

[0271] In addition, R 521 , R 522 and R 523 It may be an organic group having an oxygen atom, for example, a group having a group selected from the above-mentioned monovalent aliphatic group, alicyclic group, aromatic group, and heterocyclic group via an oxygen atom. In this case, as a monovalent organic group having a group via an oxygen atom, a group having an oxygen atom and an aliphatic group is preferred.

[0272] As such a compound (5) represented by the general formula (5-2), tri-n-octylphosphine (in the general formula (5-2), R 521 , R 522 and R 523 is 1-octyl), triphenylphosphine (in the general formula (5-2), R 521 , R 522 and R 523 In addition, compounds having the structure based on this can of course also obtain the same effect.

[0273] As the compound (5), preferably, a compound represented by the following general formula (5-3) can be mentioned.

[0274] [Chemistry 13]

[0275]

[0276] In the general formula (5-3), R 531 , R 532 , R 535 and R 536 R each independently represents an organic group. 533 and R 534 Each independently represents a single bond or an organic group, X 531 represents a single bond or an oxygen atom. In addition, R 533 and R 534 At least one of R is an organic group, 533 With R 534 They may be bonded to each other to form a condensed ring.

[0277] R 531 , R 532, R 535 and R 536 The organic group is a monovalent organic group, and examples thereof include the above-mentioned R 11 and R 12 The monovalent aliphatic group, alicyclic group, aromatic group and heterocyclic group in the organic group described for the organic group are preferably a monovalent aliphatic group or aromatic group, and more preferably a monovalent aromatic group. The monovalent aliphatic group, alicyclic group, aromatic group and heterocyclic group are the same as those in the above R 11 and R 12 The same groups are described for the organic groups.

[0278] R 531 , R 532 , R 535 and R 536 The monovalent aromatic group of R 11 and R 12 Among the aromatic groups explained as aromatic groups, the aromatic groups having a monocyclic aromatic compound as a basic structure are preferably phenyl groups.

[0279] In addition, R 531 , R 532 , R 535 and R 536 It may be an organic group having an oxygen atom, for example, a group having a group selected from the above-mentioned monovalent aliphatic group, alicyclic group, aromatic group, and heterocyclic group via an oxygen atom. In this case, as the monovalent organic group having via an oxygen atom, a group having an oxygen atom and an aliphatic group, or a group having an oxygen atom and an aromatic group is preferred.

[0280] R 533 and R 534 The organic group is a divalent organic group, and examples thereof include the above-mentioned R 11 and R 12 The divalent aliphatic group, alicyclic group, aromatic group and heterocyclic group in the organic group described for the organic group are preferably a divalent aliphatic group or aromatic group, and more preferably a divalent aromatic group. 11 and R 12 The same groups are described for the organic groups.

[0281] From the perspective of reducing oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance, R 533 and R 534 The carbon number of the divalent aliphatic group is preferably 1 or more, more preferably 2 or more, further preferably 3 or more, and the upper limit is preferably 16 or less, more preferably 12 or less, further preferably 8 or less, and further preferably 6 or less.

[0282] The aliphatic group may be straight-chain or branched, preferably straight-chain. 11 and R 12 The aliphatic groups are the same.

[0283] As R 533 and R 534 The divalent aromatic group can be used as the above R 11 and R 12 The divalent aromatic group in the aromatic group described above as an aromatic group may be a group having as a chemical bond a portion obtained by removing two hydrogen atoms from the basic structure of the above-mentioned monocyclic aromatic compound, bonded polycyclic aromatic compound, or condensed polycyclic aromatic compound, and is preferably a group having as a chemical bond a portion obtained by removing two hydrogen atoms from the basic structure of the above-mentioned monocyclic aromatic compound or condensed polycyclic aromatic compound.

[0284] R 533 and R 534 At least one of the groups is an organic group.

[0285] R 533 With R 534 can be bonded to each other to form a condensed ring. In this case, X 531 As the condensed ring in this case, there can be exemplified the following: 11 and R 12 The condensed ring described in the alicyclic group, aromatic group and heterocyclic group.

[0286] In addition, in X 531 When R is an oxygen atom, 533 , X 531 With R 534 They may also be bonded to each other to form a condensed ring. In this case, the condensed ring may be exemplified by 11 and R 12 The oxygen-containing condensed polycyclic heterocyclic compound described in the heterocyclic group.

[0287] As such a compound (5) represented by the general formula (5-3), 1,4-bis(diphenylphosphino)butane (in the general formula (5-3), R 531 , R 532 , R 535 and R 536 is phenyl, R 533 is 1,4-butanediyl, R 534 and X 531 is a single bond), bis[(2-diphenylphosphino)phenyl]ether (in the general formula (5-3), R 531 , R 532, R 535 and R 536 is phenyl, R 533 and R 534 is phenylenediyl, X 531 is an oxygen atom), 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene (in the general formula (5-3), R 531 , R 532 , R 535 and R 536 is phenyl, R 533 is xanthene-4,5-diyl, R 534 and X 531 is a single bond. In addition, it can also be said that R 533 is dihydrobenzopyranyl, R 534 is phenyl, R 533 With R 534 The compounds having the structure based on this can also obtain the same effect.

[0288] In the modified sulfide solid electrolyte of the present embodiment, the above-mentioned compound (5) can be used alone or in combination of multiple compounds, and at least one compound selected from the compound represented by the above-mentioned general formula (5-1), the compound represented by the general formula (5-2) and the compound represented by the general formula (5-3) can be used. For example, the compound represented by the above-mentioned general formula (5-1) can be used alone, or two compounds represented by the above-mentioned general formula (5-1) can be used in combination, and the same applies to the compounds represented by the above-mentioned general formulas (5-2) and (5-3). In addition, for example, the compound represented by the above-mentioned general formula (5-1) can be used alone or in combination with the compound represented by the general formula (5-2) alone or in combination with the compound represented by the general formula (5-2). The same applies to the compound represented by the general formula (5-2) and the compound represented by the general formula (5-3), and the compound represented by the general formula (5-1) and the compound represented by the general formula (5-3).

[0289] From the viewpoint of reducing oil absorption, easily obtaining excellent coating suitability, and more effectively obtaining excellent battery performance, the molecular weight of compound (5) is preferably 3000 or less, more preferably 2000 or less, further preferably 1500 or less, and further preferably 1000 or less.

[0290] (Compound (6))

[0291] The compound (6) used in the modified sulfide solid electrolyte of the present embodiment is a metal-free boron compound. The compound (6) may be any metal-free boron compound. As the compound (6), a compound represented by the following general formula (6) can be preferably exemplified. The oil absorption is reduced, and excellent coating adaptability is easily obtained, and excellent battery performance can be obtained more effectively.

[0292] [Chemistry 14]

[0293]

[0294] In the general formula (6), R 61 , R 62 and R 63 Each independently represents an organic group.

[0295] R 61 , R 62 and R 63 The organic group is a monovalent organic group, and examples thereof include the above-mentioned R 11 and R 12 Among the organic groups explained for the organic groups, monovalent aliphatic groups, alicyclic groups, aromatic groups and heterocyclic groups are preferably monovalent aliphatic groups. 11 and R 12 The same groups are described for the organic groups.

[0296] About R 61 , R 62 and R 63 The carbon number of the monovalent aliphatic group is preferably 1 or more, more preferably 2 or more, further preferably 4 or more, and further preferably 6 or more, from the viewpoint of reducing the oil absorption, easily obtaining excellent coating adaptability, and more effectively obtaining excellent battery performance. The upper limit is preferably 28 or less, more preferably 24 or less, further preferably 20 or less, and further preferably 18 or less.

[0297] The aliphatic group may be straight-chain or branched, preferably straight-chain. 11 and R 12 The aliphatic groups are the same.

[0298] In addition, R 61 , R 62 and R 63An organic group having an oxygen atom is also preferred. Examples of organic groups having an oxygen atom include groups having a group selected from the above-mentioned monovalent aliphatic group, alicyclic group, aromatic group, and heterocyclic group via an oxygen atom. In this case, as a monovalent organic group having an oxygen atom, a group having an oxygen atom and an aliphatic group is preferred, and a group having an oxygen atom and an alkyl group, i.e., an alkoxy group, is particularly preferred. The carbon number of the aliphatic group is the same as that of the above R 61 , R 62 and R 63 The monovalent aliphatic groups of are preferably the same in carbon number.

[0299] As such a compound (6) represented by the general formula (6), tri-n-octyl borate (in the general formula (6), R 61 , R 62 and R 63 is octyloxy), tri-n-octadecyl borate (in the general formula (6), R 61 , R 62 and R 63 In addition, compounds having the structure based on this can also obtain the same effect.

[0300] In the modified sulfide solid electrolyte of the present embodiment, the above-mentioned compound (6) can be used alone or in combination of two or more.

[0301] Compounds (1) to (4) and (6) are preferably compounds having a predetermined molecular weight, similarly to compound (5), from the viewpoint of easily obtaining excellent coating adaptability and more effectively obtaining excellent battery performance. Specifically, compounds (1) to (4) and (6) preferably have a molecular weight of 3000 or less, more preferably 2000 or less, further preferably 1500 or less, and further preferably 1000 or less, from the viewpoint of easily obtaining excellent coating adaptability and more effectively obtaining excellent battery performance.

[0302] The content of at least one compound selected from compounds (1) to (6) and having a molecular weight of 3000 or less is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 99% by mass or more, and further preferably 100% by mass, i.e., further preferably, the total amount thereof is compounds having a number average molecular weight of 3000 or less.

[0303] On the contrary, the content of at least one compound selected from compounds (1) to (6) having a molecular weight exceeding 3000 is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 1% by mass or less, and even more preferably 0% by mass, relative to the total amount of at least one compound selected from compounds (1) to (6) contained in the modified sulfide solid electrolyte. That is, it is even more preferred that no compound with a molecular weight exceeding 3000 is contained.

[0304] The content of the above compounds (1) to (6) contained in the modified sulfide solid electrolyte can vary depending on the type of compound used and therefore cannot be generalized, but is preferably 0.03 parts by mass or more, more preferably 0.05 parts by mass, further preferably 0.1 parts by mass or more, and further preferably 0.5 parts by mass, relative to 100 parts by mass of the sulfide solid electrolyte, and the upper limit is preferably 25 parts by mass or less, and more preferably 20 parts by mass or less. Within the above range, the coating adaptability when applied as a paste can be efficiently improved, and excellent battery performance can be more efficiently obtained.

[0305] In addition, in the modified sulfide solid electrolyte of the present embodiment, at least one compound selected from the above compounds (1) to (6) is used. That is, as in the case of using the above compounds (1) to (6) alone or in combination of a plurality of compounds belonging to compound (1), a plurality of compounds of each of compounds (1) to (6) may be used in combination, or two or more compounds selected from compounds (1) to (6) may be used in combination.

[0306] (Manufacturing of sulfide solid electrolyte)

[0307] Next, the sulfide solid electrolyte that forms the modified sulfide solid electrolyte of the present embodiment is described. The sulfide solid electrolyte that can be used in the present embodiment contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and has a BET specific surface area of ​​10 m 2 / g or more, it can be used without particular limitation, and a commercially available product can be used as it is or can be produced and used.

[0308] In the case of manufacturing and using a sulfide solid electrolyte that can be used in the present embodiment, a manufacturing method thereof is described. The sulfide solid electrolyte that can be used in the present embodiment can be obtained, for example, by the following manufacturing method: the manufacturing method includes mixing two or more raw materials selected from a compound containing at least one atom of a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom.

[0309] (raw material)

[0310] As the raw material, two or more compounds selected from compounds containing at least one atom of a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom can be used.

[0311] The compound that can be used as a raw material is a compound containing at least one of a lithium atom, a phosphorus atom, a sulfur atom and a halogen atom. More specifically, representative examples include: lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; alkali metal halides such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PB r5), various phosphorus iodides (PI3, P2I4) and other phosphorus halides; thiophosphoryl fluoride (PSF3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), thiophosphoryl fluoride dichloride (PSCl2F), thiophosphoryl fluoride dibromide (PSBr2F) and other thiophosphoryl halides; and other raw materials composed of at least two atoms selected from the above four atoms; halogen monomers such as fluorine (F2), chlorine (Cl2), bromine (Br2), iodine (I2), preferably bromine (Br2) and iodine (I2).

[0312] Compounds other than the above that can be used as raw materials include, for example, compounds containing at least one atom selected from the above four atoms and atoms other than the four atoms. More specifically, examples include: lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphoric acid compounds such as sodium phosphate and lithium phosphate; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; halogenated phosphorus oxides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); and the like.

[0313] In this embodiment, from the viewpoint of more easily obtaining a sulfide solid electrolyte with high ionic conductivity, chlorine atoms, bromine atoms, and iodine atoms are preferred among the halogen atoms, and bromine atoms and iodine atoms are more preferred. In addition, these atoms can be used alone or in combination. That is, taking lithium halide as an example, lithium bromide can be used alone, lithium iodide can be used alone, or lithium bromide and lithium iodide can be used in combination.

[0314] In addition, from the same point of view, as compounds that can be used as raw materials, among the above, lithium sulfide is preferred; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); halogen monomers such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2); lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide. Among phosphorus sulfides, phosphorus pentasulfide is preferred; among halogen monomers, chlorine (Cl2), bromine (Br2), and iodine (I2) are preferred; and among lithium halides, lithium chloride, lithium bromide, and lithium iodide are preferred.

[0315] As combinations of compounds that can be used as raw materials, for example, combinations of lithium sulfide, phosphorus pentasulfide and lithium halides, and combinations of lithium sulfide, phosphorus pentasulfide and halogen monomers can be preferably mentioned. Lithium bromide, lithium iodide and lithium chloride are preferred as lithium halides, and chlorine, bromine and iodine are preferred as halogen monomers.

[0316] In the present embodiment, when lithium sulfide is used as the compound containing lithium atoms, the lithium sulfide is preferably in the form of particles.

[0317] The average particle size of lithium sulfide particles (D 50 ) is preferably 10 μm to 2000 μm, more preferably 30 μm to 1500 μm, and even more preferably 50 μm to 1000 μm. In this specification, the average particle size (D 50 ) is the particle size when the particle size distribution cumulative curve is drawn from the smallest particle to 50% of the total, and the volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device. In addition, among the substances exemplified as the above-mentioned raw materials, the solid raw material preferably has an average particle size of the same degree as the above-mentioned lithium sulfide particles, that is, the average particle size is preferably within the same range as the average particle size of the above-mentioned lithium sulfide particles.

[0318] When lithium sulfide, phosphorus pentasulfide and lithium halide are used as raw materials, from the viewpoint of obtaining higher chemical stability and the viewpoint of increasing the PS4 fraction and obtaining high ion conductivity, the ratio of lithium sulfide to the total of lithium sulfide and phosphorus pentasulfide is preferably 60 mol% or more, more preferably 65 mol% or more, further preferably 68 mol% or more, and the upper limit is preferably 80 mol% or less, more preferably 78 mol% or less, further preferably 76 mol% or less.

[0319] When lithium sulfide, phosphorus pentasulfide, lithium halide, and other raw materials used as needed are used, the content of lithium sulfide and phosphorus pentasulfide relative to the total of these is preferably 60 mol% or more, more preferably 65 mol% or more, and further preferably 70 mol% or more, and the upper limit is preferably 100 mol% or less, more preferably 90 mol% or less, and further preferably 80 mol% or less.

[0320] In addition, when lithium bromide and lithium iodide are used in combination as lithium halides, from the viewpoint of increasing the PS4 fraction and obtaining high ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 mol% or more, more preferably 20 mol% or more, further preferably 40 mol% or more, further preferably 50 mol% or more, and the upper limit is preferably 99 mol% or less, more preferably 90 mol% or less, further preferably 80 mol% or less, further preferably 70 mol% or less.

[0321] When a halogen monomer is used as a raw material and lithium sulfide and phosphorus pentasulfide are used, the ratio of the mole number of lithium sulfide obtained by removing the same mole number of lithium sulfide as the mole number of the halogen monomer to the total mole number of lithium sulfide and phosphorus pentasulfide obtained by removing the same mole number of lithium sulfide as the mole number of the halogen monomer is preferably in the range of 60 to 90%, more preferably in the range of 65 to 85%, further preferably in the range of 68 to 82%, further preferably in the range of 72 to 78%, and particularly preferably in the range of 73 to 77%. This is because higher ion conductivity can be obtained if these ratios are used. In addition, from the same viewpoint, when lithium sulfide, phosphorus pentasulfide and a halogen monomer are used, the content of the halogen monomer relative to the total amount of lithium sulfide, phosphorus pentasulfide and the halogen monomer is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, further preferably 3 to 25 mol%, and further preferably 3 to 15 mol%.

[0322] When lithium sulfide, phosphorus pentasulfide, a halogen monomer and a lithium halide are used, the content of the halogen monomer relative to the total amount of these (α mol%) and the content of the lithium halide relative to the total amount of these (β mol%) preferably satisfy the following formula (1), more preferably satisfy the following formula (2), further preferably satisfy the following formula (3), and further preferably satisfy the following formula (4).

[0323] 2≤2α+β≤100…(1)

[0324] 4≤2α+β≤80…(2)

[0325] 6≤2α+β≤50…(3)

[0326] 6≤2α+β≤30…(4)

[0327] (mix)

[0328] The mixing of two or more raw materials selected from compounds containing at least one of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms can be performed by mixing the raw materials using, for example, a mixer, a stirrer, a pulverizer or the like.

[0329] This is because the raw materials can be mixed even when a stirrer is used, and when a pulverizer is used, the raw materials are pulverized and mixed at the same time. That is, it can be said that the sulfide solid electrolyte used in the present embodiment can be mixed by stirring, mixing, pulverizing, or any combination of two or more raw materials selected from compounds containing at least one of lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms.

[0330] As agitators and mixers, for example, a mechanical stirring mixer having stirring blades in a reaction tank and capable of stirring (also referred to as mixing brought by stirring, stirring and mixing) can be exemplified. As mechanical stirring mixers, high-speed stirring mixers, double-arm mixers, etc. can be exemplified. In addition, as high-speed stirring mixers, vertical axis rotating mixers, horizontal axis rotating mixers, etc. can be exemplified, and any type of mixer can also be used.

[0331] The shape of the stirring blade used in the mechanical stirring mixer may be a blade type, an arm type, an anchor type, a paddle type, a stirring paddle type, a belt type, a multi-stage blade type, a double-arm type, a bucket type, a double-shaft blade type, a flat blade type, a C-blade type, etc. From the viewpoint of more efficiently promoting the reaction of the raw materials, a bucket type, a flat blade type, a C-blade type, an anchor type, a paddle type, a stirring paddle type is preferred, and an anchor type, a paddle type, a stirring paddle type is more preferred.

[0332] When a mechanical stirring mixer is used, the rotation speed of the stirring blade can be appropriately adjusted according to the capacity, temperature, shape of the stirring blade, etc. of the fluid in the reaction tank, without any particular limitation, and is usually set to about 5 rpm to about 400 rpm. From the viewpoint of more efficiently promoting the reaction of the raw materials, it is preferably 10 rpm to 300 rpm, more preferably 15 rpm to 250 rpm, and further preferably 20 rpm to 200 rpm.

[0333] The temperature conditions for mixing using a mixer are not particularly limited, and are, for example, usually -30 to 120° C., preferably -10 to 100° C., more preferably 0 to 80° C., and further preferably 10 to 60° C. The mixing time is usually 0.1 to 500 hours, and is preferably 1 to 450 hours, more preferably 10 to 425 hours, further preferably 20 to 400 hours, and further preferably 40 to 375 hours from the viewpoint of making the dispersion state of the raw materials more uniform and promoting the reaction.

[0334] The method of mixing with pulverization using a pulverizer is a method conventionally adopted as a solid phase method (mechanical grinding method). As the pulverizer, for example, a media type pulverizer using pulverizing media can be used.

[0335] The media pulverizer is roughly divided into a container-driven pulverizer and a media-stirring pulverizer. As the container-driven pulverizer, a stirring tank, a crushing tank, or a ball mill or a bead mill in which these are combined can be cited. In addition, as the media-stirring pulverizer, there can be cited: impact pulverizers such as a cutter mill, a hammer mill, and a pin mill; tower-type pulverizers such as a tower mill; stirring tank-type pulverizers such as a grinder, a wet sand mill (aquamizer), and a sand mill; flow-through trough-type pulverizers such as a viscose mill and a coarse crusher; flow-through tube-type pulverizers; annular pulverizers such as a combined ball mill; a continuous dynamic pulverizer; various pulverizers such as a single-shaft or multi-shaft kneading machine. Among them, if the ease of adjusting the particle size of the obtained sulfide is considered, the ball mill and bead mill exemplified as the container-driven pulverizer are preferred, and a planetary pulverizer is preferred.

[0336] These pulverizers can be appropriately selected according to the desired scale, etc. For a relatively small scale, a container-driven pulverizer such as a ball mill or a bead mill can be used. In the case of large-scale or mass production, other types of pulverizers can also be used.

[0337] Furthermore, as described later, when the mixture is in a liquid state accompanied with a liquid such as a solvent or in a slurry state during mixing, a wet pulverizer capable of wet pulverization is preferred.

[0338] As wet pulverizers, wet bead mills, wet ball mills, wet vibration mills, etc. can be representatively cited. From the perspective of being able to freely adjust the conditions of the pulverization operation and being easy to handle materials with smaller particle sizes, wet bead mills using beads as pulverization media are preferred. In addition, dry pulverizers such as dry bead mills, dry ball mills, dry vibration mills, and dry non-media pulverizers such as jet mills can also be used.

[0339] In addition, when the object to be mixed is in a liquid state or a slurry state, a flow-through pulverizer can be used, which can be circulated as needed. Specifically, a pulverizer that circulates between a pulverizer (pulverizing mixer) for pulverizing slurry and a temperature-maintaining tank (reaction container) can be cited.

[0340] The size of the beads or balls used in the above-mentioned ball mill or bead mill can be appropriately selected according to the desired particle size, processing volume, etc. For example, the diameter of the beads is usually 0.05 mmφ or more, preferably 0.1 mmφ or more, more preferably 0.3 mmφ or more, and the upper limit is usually 5.0 mmφ or less, preferably 3.0 mmφ or less, and more preferably 2.0 mmφ or less. In addition, the diameter of the balls is usually 2.0 mmφ or more, preferably 2.5 mmφ or more, and more preferably 3.0 mmφ or more, and the upper limit is usually 20.0 mmφ or less, preferably 15.0 mmφ or less, and more preferably 10.0 mmφ or less.

[0341] In addition, examples of the material include metals such as stainless steel, chrome steel, and tungsten carbide; ceramics such as zirconium oxide and silicon nitride; and minerals such as agate.

[0342] When a ball mill or a bead mill is used, the rotation speed cannot be generally specified because it varies according to the scale of treatment, but is usually 10 rpm or more, preferably 20 rpm or more, and more preferably 50 rpm or more, and the upper limit is usually 1,000 rpm or less, preferably 900 rpm or less, more preferably 800 rpm or less, and further preferably 700 rpm or less.

[0343] The pulverization time in this case cannot be generally stated because it varies depending on the scale of treatment, but is usually 0.5 hours or more, preferably 1 hour or more, more preferably 5 hours or more, and further preferably 10 hours or more, and the upper limit is usually 100 hours or less, preferably 72 hours or less, more preferably 48 hours or less, and further preferably 36 hours or less.

[0344] By selecting the size and material of the medium (beads, balls) used, the rotation speed and time of the rotor, etc., mixing, stirring, pulverization, or any combination of these can be performed, and the particle size of the obtained sulfide can be adjusted.

[0345] (Solvent)

[0346] When the above-mentioned mixing is performed, a solvent may be added to the above-mentioned raw materials for mixing. As the solvent, various solvents called organic solvents and the like can be widely used.

[0347] As the solvent, a wide range of solvents conventionally used in the production of solid electrolytes can be adopted, and examples thereof include hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents.

[0348] Examples of aliphatic hydrocarbons include hexane, pentane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane and tridecane. Examples of alicyclic hydrocarbons include cyclohexane and methylcyclohexane. Examples of aromatic hydrocarbon solvents include benzene, toluene, xylene, mesitylene, ethylbenzene, tert-butylbenzene, trifluoromethylbenzene and nitrobenzene.

[0349] In addition to the above-mentioned hydrocarbon solvents, solvents containing atoms other than carbon atoms and hydrogen atoms, such as nitrogen atoms, oxygen atoms, sulfur atoms, halogen atoms and other heteroatoms, can also be exemplified. Such solvents have the property of easily forming complexes with compounds containing lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms used as raw materials (hereinafter, such solvents are also referred to as "complexing agents"), and have the property of making halogen atoms easily remain in the structure of the sulfide solid electrolyte, so they are useful in obtaining higher ion conductivity. As such complexing agents, in addition to ether solvents and ester solvents containing oxygen atoms as heteroatoms, alcohol solvents, aldehyde solvents and ketone solvents can also be preferably exemplified.

[0350] As the ether solvent, for example, preferably there can be mentioned aliphatic ethers such as dimethyl ether, diethyl ether, tert-butyl methyl ether, dimethoxymethane, dimethoxyethane, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme) or diethylene glycol, triethylene glycol; alicyclic ethers such as ethylene oxide, propylene oxide, tetrahydrofuran, tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane; heterocyclic ethers such as furan, benzofuran, benzopyran; aromatic ethers such as methyl phenyl ether (anisole), ethyl phenyl ether, dibenzyl ether, diphenyl ether.

[0351] As the ester solvent, for example, preferably exemplified are methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate; aliphatic esters such as methyl propionate, ethyl propionate, dimethyl oxalate, diethyl oxalate, dimethyl malonate, diethyl malonate, dimethyl succinate, diethyl succinate; alicyclic esters such as methyl cyclohexanecarboxylate, ethyl cyclohexanecarboxylate, dimethyl cyclohexanedicarboxylate; heterocyclic esters such as methyl pyridinecarboxylate, methyl pyrimidinecarboxylate, acetyl lactone, propiolactone, butyrolactone, valerolactone; aromatic esters such as methyl benzoate, ethyl benzoate, dimethyl phthalate, diethyl phthalate, butyl benzyl phthalate, dicyclohexyl phthalate, trimethyl trimellitate, triethyl trimellitate.

[0352] In addition, preferably, there can be mentioned alcohol solvents such as ethanol and butanol; aldehyde solvents such as formaldehyde, acetaldehyde and dimethylformamide; ketone solvents such as acetone and methyl ethyl ketone.

[0353] Examples of the solvent containing a nitrogen atom as a hetero atom include solvents having a group containing a nitrogen atom such as an amino group, an amide group, a nitro group or a nitrile group.

[0354] For example, as the solvent having an amino group, preferably exemplified are aliphatic amines such as ethylenediamine, diaminopropane, dimethylethylenediamine, diethylethylenediamine, dimethyldiaminopropane, tetramethyldiaminomethane, tetramethylethylenediamine (TMEDA), and tetramethyldiaminopropane (TMPDA); alicyclic amines such as cyclopropanediamine, cyclohexanediamine, and bisaminomethylcyclohexane; heterocyclic amines such as isophoronediamine, piperazine, dipiperidylpropane, and dimethylpiperazine; and aromatic amines such as phenylenediamine, toluenediamine, naphthalenediamine, methylphenylenediamine, dimethylnaphthalenediamine, dimethylphenylenediamine, tetramethylphenylenediamine, and tetramethylnaphthalenediamine.

[0355] Also preferably, there can be mentioned nitrile solvents such as acetonitrile and acrylonitrile; and solvents containing nitrogen atoms such as dimethylformamide, nitrobenzene and dimethylacetamide.

[0356] As the solvent containing a halogen atom as a hetero atom, preferably, chloroform, carbon tetrachloride, dichloromethane, chlorobenzene, dichlorobenzene, trifluoromethylbenzene, chlorotoluene, bromobenzene and the like are exemplified.

[0357] Furthermore, as the solvent containing a sulfur atom, dimethyl sulfoxide, carbon disulfide, etc. can be preferably exemplified.

[0358] When using a solvent, the usage amount of the solvent is preferably more than 100 mL relative to the total amount 1kg of the raw material, more preferably more than 200 mL, further preferably more than 250 mL, more preferably more than 300 mL, and as the upper limit is preferably below 3000 mL, more preferably below 2500 mL, further preferably below 2000 mL, and further preferably below 1550 mL. If the usage amount of the solvent is within the above range, the raw material reaction can be efficiently made.

[0359] (dry)

[0360] In the case of using a solvent for mixing, the fluid (usually a slurry) obtained by mixing may be dried after mixing. In the case of using a complexing agent as a solvent, the sulfide solid electrolyte can be obtained by removing the complexing agent from the complex containing the complexing agent, and in the case of using a complexing agent and a solvent in combination, by removing the complexing agent from the complex containing the complexing agent and removing the solvent, and in the case of using a solvent other than a complexing agent, by removing the solvent. The obtained sulfide solid electrolyte exhibits ionic conductivity caused by lithium atoms.

[0361] The fluid obtained by mixing can be dried at a temperature corresponding to the type of solvent, for example, at a temperature equal to or higher than the boiling point of the complexing agent.

[0362] Furthermore, the complexing agent and the solvent used as required can be dried by volatilizing them by using a vacuum pump or the like under reduced pressure (vacuum drying) at usually 5 to 100°C, preferably 10 to 85°C, more preferably 15 to 70°C, and still more preferably around room temperature (23°C) (e.g. around room temperature ±5°C).

[0363] The fluid may also be dried by filtration using a glass filter, solid-liquid separation by decantation, or solid-liquid separation using a centrifuge. When a solvent other than a complexing agent is used, a sulfide solid electrolyte can be obtained by solid-liquid separation. In addition, when a complexing agent is used as a solvent, after solid-liquid separation, drying under the above-mentioned temperature conditions is performed to remove the complexing agent introduced into the complex.

[0364] Specifically, as a solid-liquid separation, the fluid is transferred to a container, and after the sulfide (or the complex (a substance that can be called a precursor of a sulfide solid electrolyte)) is precipitated, it is easier to remove the complexing agent and solvent that become the supernatant by decantation or by filtering using, for example, a glass filter with a pore size of about 10 to 200 μm, preferably 20 to 150 μm.

[0365] Drying may be performed after mixing and before the hydrogen treatment described below, or after the hydrogen treatment.

[0366] The sulfide solid electrolyte obtained by the above mixing, or the sulfide solid electrolyte obtained by removing the solvent by the above drying when a solvent is used, expresses ion conductivity due to lithium atoms.

[0367] The sulfide solid electrolyte obtained by the above mixing basically becomes an amorphous sulfide solid electrolyte (glass component) unless the mixture is pulverized to a degree of crystallization using a pulverizer, for example.

[0368] The sulfide solid electrolyte obtained by the above mixing may be an amorphous sulfide solid electrolyte (glass component) or a crystalline sulfide solid electrolyte, and can be appropriately selected as desired. When a crystalline sulfide solid electrolyte is produced, the amorphous sulfide solid electrolyte obtained by the above mixing is heated to produce a crystalline sulfide solid electrolyte.

[0369] As a sulfide solid electrolyte, in order to adjust the particle size of the powder of the crystalline sulfide solid electrolyte, after subjecting it to a treatment such as pulverization described later, a crystalline sulfide solid electrolyte having an amorphous component (glass component) formed on its surface may be included. Therefore, the sulfide solid electrolyte containing an amorphous component also includes an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte having an amorphous component formed on its surface.

[0370] (heating)

[0371] When a crystalline sulfide solid electrolyte is produced, heating may be further included. When an amorphous sulfide solid electrolyte (glass component) is obtained by the above mixing, a crystalline sulfide solid electrolyte can be obtained by heating, and when a crystalline sulfide solid electrolyte is obtained, a crystalline sulfide solid electrolyte with improved crystallinity can be obtained.

[0372] In addition, when a complexing agent is used as a solvent during mixing, although a complex containing the complexing agent is formed, the complexing agent can be removed from the complex by heating without the above-mentioned drying to obtain a sulfide solid electrolyte. Depending on the heating conditions, an amorphous substance can be made, and a crystalline substance can be made.

[0373] Regarding the heating temperature, for example, in the case of obtaining an amorphous sulfide solid electrolyte, the heating temperature may be determined according to the structure of the crystalline sulfide solid electrolyte obtained by heating the amorphous sulfide solid electrolyte. Specifically, the amorphous sulfide solid electrolyte is subjected to differential thermal analysis (DTA) using a differential thermal analyzer (DTA apparatus) under a temperature increase condition of 10°C / min, and the temperature of the peak top of the exothermic peak observed on the lowest temperature side is preferably set to a range of 5°C or less, more preferably 10°C or less, and further preferably 20°C or less, with the lower limit not particularly limited, but may be set to a temperature of the peak top of the exothermic peak observed on the lowest temperature side of about -40°C or more. By setting the temperature in such a range, an amorphous sulfide solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining an amorphous sulfide solid electrolyte varies depending on the structure of the obtained crystalline sulfide solid electrolyte and cannot be generally specified, but is usually preferably 135°C or lower, more preferably 130°C or lower, and further preferably 125°C or lower. The lower limit is not particularly limited, but is preferably 90°C or higher, more preferably 100°C or higher, and further preferably 105°C or higher.

[0374] In addition, when heating an amorphous sulfide solid electrolyte to obtain a crystalline sulfide solid electrolyte, the heating temperature may be determined according to the structure of the crystalline sulfide solid electrolyte, and is preferably higher than the above-mentioned heating temperature for obtaining an amorphous sulfide solid electrolyte. Specifically, the amorphous sulfide solid electrolyte is subjected to differential thermal analysis (DTA) using a differential thermal analyzer (DTA device) under a temperature increase condition of 10°C / min, and the temperature of the peak top of the exothermic peak observed on the lowest temperature side is preferably set to 5°C or more, more preferably 10°C or more, and further preferably 20°C or more. The upper limit is not particularly limited, but may be about 40°C or less. By setting the temperature in such a range, a crystalline sulfide solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining a crystalline sulfide solid electrolyte varies depending on the composition and structure of the obtained crystalline sulfide solid electrolyte and cannot be generally specified, but is usually preferably 130° C. or higher, more preferably 135° C. or higher, and further preferably 140° C. or higher. The upper limit is not particularly limited, but is preferably 600° C. or lower, more preferably 550° C. or lower, and further preferably 500° C. or lower.

[0375] The heating time is not particularly limited as long as it is a time for obtaining the desired amorphous sulfide solid electrolyte or crystalline sulfide solid electrolyte, and is, for example, preferably 1 minute or more, more preferably 10 minutes or more, further preferably 30 minutes or more, and further preferably 1 hour or more. In addition, the upper limit of the heating time is not particularly limited, but is preferably 24 hours or less, more preferably 10 hours or less, further preferably 5 hours or less, and further preferably 3 hours or less.

[0376] In addition, heating is preferably performed in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or in a reduced pressure atmosphere (particularly in a vacuum). For example, an inert gas atmosphere containing a certain concentration of hydrogen may also be used. This is because it is possible to prevent degradation (e.g., oxidation) of the crystalline sulfide solid electrolyte.

[0377] The heating method is not particularly limited, and examples thereof include methods using a hot plate, a vacuum heating device, an argon atmosphere furnace, a firing furnace, etc. In addition, in industry, a horizontal dryer or a horizontal vibrating fluidized dryer having a heating unit and a feeding mechanism can also be used, and the method can be selected according to the amount of heating treatment.

[0378] (Sulfide solid electrolyte)

[0379] As described above, the sulfide solid electrolyte used in the present embodiment may be a commercially available product or a manufactured sulfide solid electrolyte.

[0380] The sulfide solid electrolyte obtained by the above method is an amorphous (glass component) or crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and is preferably used as the sulfide solid electrolyte in the present embodiment.

[0381] (BET specific surface area)

[0382] Regarding the specific surface area of ​​the sulfide solid electrolyte used in this embodiment, the BET specific surface area is 10 m 2 / g or more. Although the modified sulfide solid electrolyte of this embodiment has a large specific surface area as described above, it has excellent coating adaptability when applied as a paste and can effectively demonstrate excellent battery performance. The higher the BET specific surface area of ​​the sulfide solid electrolyte, the more the advantage of this effect can be further demonstrated. From this point of view, the BET specific surface area is preferably 12m 2 / g or more, more preferably 15m 2 / g or more, more preferably 20m 2 From the same point of view, there is no particular upper limit, but it is actually 100 m 2 / g or less, preferably 75m 2 / g or less, more preferably 50m 2 / g or less.

[0383] In this specification, the BET specific surface area is a specific surface area measured using krypton gas as an adsorbent in accordance with JIS Z 8830:2013 (method for measuring specific surface area of ​​powders (solids) by gas adsorption).

[0384] (Amorphous sulfide solid electrolyte)

[0385] As the amorphous sulfide solid electrolyte obtained by the above method, it contains lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc., can be preferably exemplified; and solid electrolytes such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc., which contain other atoms such as oxygen atoms and silicon atoms. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc., can be preferably exemplified.

[0386] The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an inductively coupled plasma (ICP) emission spectrometer.

[0387] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) For example, the range of 0.01 μm to 500 μm and 0.1 to 200 μm can be exemplified.

[0388] (Crystalline sulfide solid electrolyte)

[0389] The crystalline sulfide solid electrolyte obtained by the above method can be a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a temperature above the crystallization temperature. As its crystal structure, Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0390] In addition, Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICONRegion II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x S4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). From the perspective of obtaining higher ionic conductivity, the crystal structure of the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment is preferably a thio-LISICON Region II type crystal structure among the above. Here, "thio-LISICON Region II type crystal structure" means Li 4-x Ge 1-x P x S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x Px Any crystal structure similar to the S4 type thio-LISICON Region II type crystal structure. In addition, the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment can be a crystalline sulfide solid electrolyte having the above-mentioned thio-LISICON Region II type crystal structure, or it can be a crystalline sulfide solid electrolyte having the thio-LISICON Region II type crystal structure as the main crystal. From the viewpoint of obtaining higher ionic conductivity, it is preferred to have the thio-LISICON Region II type crystal structure as the main crystal. In this specification, "having as the main crystal" means that the proportion of the crystal structure as the object in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, from the viewpoint of obtaining higher ionic conductivity, the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment preferably does not contain crystalline Li3PS4 (β-Li3PS4).

[0391] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.

[0392] As described above, in the case of obtaining the crystal structure of the sulfide crystalline lithium superionic conductor region II in this embodiment, it is preferably free of crystalline Li3PS4 (β-Li3PS4). The sulfide solid electrolyte obtained by the manufacturing method of this embodiment does not have diffraction peaks at 2θ = 17.5° and 26.1° that can be observed in crystalline Li3PS4, or even if it has them, it only has peaks at a level that is extremely small compared to the diffraction peaks of the crystal structure of the sulfide crystalline lithium superionic conductor region II.

[0393] The above crystal structure in which a part of P is substituted by Si in the structural framework of Li7PS6 and represented by the composition formula Li 7-x P 1- y Si y S6 and Li 7+x P 1-y Si y S6 (where x is -0.6 to 0.6 and y is 0.1 to 0.6) is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. The above crystal structure represented by the composition formula Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) is preferably cubic, and in X-ray diffraction measurement using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. In addition, the above crystal structure represented by the composition formula Li 7-x PS 6-x Ha x (where Ha is Cl or Br and x is preferably 0.2 to 1.8) is preferably cubic, and in X-ray diffraction measurement using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. These crystal structures basically having the structural framework of Li7PS6 are also called argyrodite-type crystal structures.

[0394] In addition, these peak positions can fluctuate within a range of ±0.5°.

[0395] As the shape of the crystalline sulfide solid electrolyte, there is no particular limitation, and for example, particulate form can be cited. The average particle diameter (D 50) For example, the range of 0.01 μm to 500 μm and 0.1 to 200 μm can be exemplified.

[0396] (Properties of modified sulfide solid electrolyte)

[0397] The modified sulfide solid electrolyte of this embodiment has a BET specific surface area of ​​10 m 2 / g or more, having a larger specific surface area. The higher the BET specific surface area of ​​the sulfide solid electrolyte, the more advantageous this effect can be shown. From this point of view, the BET specific surface area is preferably 12 m 2 / g or more, more preferably 15m 2 / g or more, more preferably 20m 2 From the same point of view, there is no particular upper limit, but it is actually 100 m 2 / g or less, preferably 75m 2 / g or less, more preferably 50m 2 / g or less.

[0398] Even if lithium halide is attached to the surface, it will not have a significant effect on the BET specific surface area of ​​the sulfide solid electrolyte. The BET specific surface area of ​​the sulfide solid electrolyte used in this embodiment is substantially the same as the BET specific surface area of ​​the modified sulfide solid electrolyte. Therefore, as described above, as long as a BET specific surface area of ​​10 m 2 / g or more sulfide solid electrolyte as the sulfide solid electrolyte, the BET specific surface area of ​​the modified sulfide solid electrolyte will naturally become 10m 2 / g or above.

[0399] Regarding the oil absorption of the modified sulfide solid electrolyte of the present embodiment, the BET specific surface area is large as described above, but due to the effect of the compounds (1) to (6) attached to the surface, it is usually small and is 1.10 mL / g or less, and further 1.00 mL / g or less, 0.90 mL / g or less, 0.85 mL / g or less, and 0.80 mL / g or less. Although the modified sulfide solid electrolyte of the present embodiment has a large BET specific surface area, due to the small oil absorption, when it is made into a paste, the increase in the viscosity of the paste can be suppressed, and the coating adaptability during coating is excellent. There is no need to use a solvent or the like to suppress the increase in the viscosity of the paste, so it is easy to obtain excellent battery performance.

[0400] In this specification, regarding the oil absorption, 1 g of the modified sulfide solid electrolyte is used as a sample, 1 drop of butyl butyrate is added to a mortar or the like, and then stirred with a spatula, and this operation is repeated until the sample becomes a paste, and the total amount of butyl butyrate added is defined as the oil absorption (mL / g). Here, "paste" refers to a state of "a substance that can be extended without breaking or becoming broken and slightly adheres to a measuring plate" as specified in "7.2 Measurement" of JIS K5101-13-1:2004 (Testing Methods for Pigments - Part 13: Oil Absorption - Section 1: Refined Linseed Oil Method).

[0401] In addition, the ion conductivity of the modified sulfide solid electrolyte of this embodiment is usually 0.5 mS / cm or more, further 1.0 mS / cm or more, 1.5 mS / cm or more, 2.0 mS / cm or more, and 2.5 mS / cm or more, and has extremely high ion conductivity, and a lithium battery with excellent battery performance can be obtained.

[0402] (use)

[0403] The modified sulfide solid electrolyte of this embodiment has excellent coating adaptability and can be used in the manufacture of batteries even without using solvents, so it can effectively demonstrate excellent battery performance. In addition, it has high ion conductivity and excellent battery performance, so it is preferably used in batteries.

[0404] The modified sulfide solid electrolyte of this embodiment can be used for the positive electrode layer, the negative electrode layer, or the electrolyte layer. In addition, each layer can be produced by a known method.

[0405] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a substance that reacts with the solid electrolyte such as Au, Pt, Al, Ti or Cu can be used.

[0406] [Method for producing modified sulfide solid electrolyte]

[0407] The method for producing the modified sulfide solid electrolyte of this embodiment includes:

[0408] The BET specific surface area is 10m 2 / g or more of a sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, at least one compound selected from the following compounds (1) to (6), and an organic solvent; and

[0409] The organic solvent is removed.

[0410] According to the production method of the present embodiment, the modified sulfide solid electrolyte of the present embodiment described above can be efficiently produced. That is, the modified sulfide solid electrolyte of the present embodiment is preferably produced by the production method of the present embodiment.

[0411] Compound (1) a compound having a formyl group (CH(=O)-);

[0412] Compound (2) a compound having one or more acetyl groups (CH3C(=O)-);

[0413] Compound (3) a compound having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom, a chlorine atom, a bromine atom or an iodine atom) and an organic group;

[0414] Compound (4) a thiol compound;

[0415] Compound (5) a metal-free phosphorus compound (wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom);

[0416] Compound (6) is a boron compound containing no metal.

[0417] Regarding compound (3) having two or more halogen-containing groups represented by -CH2X (X represents a fluorine atom, a chlorine atom, a bromine atom or an iodine atom) and an organic group, the halogen atom of X is preferably a fluorine atom or a bromine atom.

[0418] The BET specific surface area used in the production method of this embodiment is 10 m 2 The sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms in an amount of 100 g or more is the same sulfide solid electrolyte as that described as being usable in the modified sulfide solid electrolyte of the present embodiment. Therefore, as the sulfide solid electrolyte, a commercially available product can be used, and a sulfide solid electrolyte produced by the method of the sulfide solid electrolyte can also be used.

[0419] As the organic solvent used in the production method of the present embodiment, for example, the solvents described as the solvents that can be used in the method for producing the above-mentioned sulfide solid electrolyte can be exemplified. From the viewpoint of promoting mixing of the sulfide solid electrolyte and the heteropolycyclic compound, efficiently obtaining a modified sulfide solid electrolyte containing the sulfide solid electrolyte and the heteropolycyclic compound, and from the viewpoint of promoting adhesion of the heteropolycyclic compound to the sulfide solid electrolyte, among the above-mentioned solvents, preferably, an aliphatic hydrocarbon solvent, an alicyclic hydrocarbon solvent, an aromatic hydrocarbon solvent, and the ether solvent, ester solvent, and nitrile solvent exemplified as a complexing agent can be exemplified, and an aromatic hydrocarbon solvent is more preferable.

[0420] In the production method of the present embodiment, as the organic solvent, one kind among these can be used alone or in combination of two or more kinds.

[0421] In the production method of the present embodiment, the method of mixing the sulfide solid electrolyte, the heteropolycyclic compound, and the organic solvent can be performed by the same method as the "mixing" in the method of producing the sulfide solid electrolyte described above.

[0422] The organic solvent can be removed by the same method as the “drying” in the method for producing the above-mentioned sulfide solid electrolyte.

[0423] In addition, in the production method of the present embodiment, the “heating” in the method for producing the above-mentioned sulfide solid electrolyte may be performed.

[0424] 〔Electrode composite materials〕

[0425] The electrode composite material of the present embodiment is an electrode composite material including the modified sulfide solid electrolyte of the present embodiment described above and an electrode active material, or an electrode composite material including the modified sulfide solid electrolyte of the other embodiment described above and an electrode active material.

[0426] (Electrode Active Material)

[0427] As the electrode active material, a positive electrode active material or a negative electrode active material is used, depending on whether the electrode composite material is used for a positive electrode or a negative electrode.

[0428] As the positive electrode active material, any positive electrode active material can be used without particular limitation as long as it can promote the battery chemical reaction through the relationship with the negative electrode active material, and the battery chemical reaction is accompanied by the movement of lithium ions caused by the atom adopted as the atom reflecting ionic conductivity, preferably the lithium atom. As the positive electrode active material that can carry out such insertion and extraction of lithium ions, oxide-based positive electrode active materials, sulfide-based positive electrode active materials, etc. can be cited.

[0429] As oxide-based positive electrode active materials, preferred examples include lithium-containing transition metal composite oxides such as LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel manganese cobalt oxide), NCA (lithium nickel cobalt aluminum oxide), LNCO (lithium nickel cobalt oxide), and olivine-type compounds (LiMeNPO4, Me = Fe, Co, Ni, Mn).

[0430] Examples of the sulfide-based positive electrode active material include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2).

[0431] In addition to the above-mentioned positive electrode active materials, niobium selenide (NbSe 3 ) or the like can also be used.

[0432] The positive electrode active material can be used alone or in combination of two or more.

[0433] As the negative electrode active material, any negative electrode active material that can promote a battery chemical reaction accompanied by the movement of lithium ions caused by an atom that embodies ionic conductivity, preferably a metal that can form an alloy with lithium atoms, an oxide thereof, an alloy of the metal and lithium atoms, etc., preferably lithium atoms, can be used without particular limitation. As such a negative electrode active material that can allow lithium ions to be inserted and removed, a substance that is known as a negative electrode active material in the battery field can be used without limitation.

[0434] Examples of such negative electrode active materials include metallic lithium such as metallic lithium, metallic indium, metallic aluminum, metallic silicon, and metallic tin, or metals capable of forming alloys with metallic lithium, oxides of these metals, and alloys of these metals with metallic lithium.

[0435] The electrode active material used in the present embodiment may have a coating layer coated on its surface.

[0436] As a material for forming the coating layer, an atom that exhibits ionic conductivity in the sulfide solid electrolyte, preferably a nitride, an oxide, or an ion conductor such as a composite of lithium atoms, can be cited. Specifically, lithium nitride (Li3N), a Li4GeO4-based structure such as Li 4-2x Zn x Conductors with LISICON crystal structures such as GeO4, and conductors with Li3PO4 skeleton structures such as Li 4-x Ge 1-x P x Conductors with sulfide-LISICON crystal structures such as S4, La 2 / 3- x Li 3x Conductors with a perovskite crystal structure such as TiO3, conductors with a NASICON crystal structure such as LiTi2(PO4)3, etc.

[0437] In addition, Li y Ti 3-y O4(0 <y<3)、Li4Ti5O 12Lithium titanate (LTO), lithium metal oxides of metals belonging to Group 5 of the periodic table such as LiNbO3, LiTaO3, and oxide-based conductors such as Li2O-B2O3-P2O5, Li2O-B2O3-ZnO, and Li2O-Al2O3-SiO2-P2O5-TiO2.

[0438] The electrode active material having a coating layer is obtained by, for example, attaching a solution containing various atoms constituting a coating layer forming material to the surface of the electrode active material and calcining the attached electrode active material preferably at 200° C. to 400° C.

[0439] Here, as the solution containing various atoms, for example, a solution containing alkoxides of various metals such as lithium ethoxide, titanium isopropoxide, niobium isopropoxide, tantalum isopropoxide, etc. can be used. At this time, as the solvent, an alcohol solvent such as ethanol and butanol; an aliphatic hydrocarbon solvent such as hexane, heptane, octane; an aromatic hydrocarbon solvent such as benzene, toluene, xylene, etc. can be used.

[0440] In addition, the above-mentioned attachment may be performed by dipping, spraying, or the like.

[0441] From the viewpoint of improving manufacturing efficiency and battery performance, the firing temperature is preferably 200° C. to 400° C., more preferably 250° C. to 390° C., and the firing time is usually about 1 minute to 10 hours, preferably 10 minutes to 4 hours.

[0442] As the coating rate of the coating layer, based on the surface area of ​​the electrode active material, it is preferably more than 90%, more preferably more than 95%, and further preferably 100%, that is, preferably the entire surface is coated. In addition, as the thickness of the coating layer, it is preferably more than 1nm, more preferably more than 2nm, and as the upper limit, it is preferably below 30nm, more preferably below 25nm.

[0443] The thickness of the coating layer can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage can be calculated from the thickness of the coating layer, elemental analysis values, and BET specific surface area.

[0444] (Other ingredients)

[0445] The electrode composite material of this embodiment may include other components such as a conductive material and a binder in addition to the modified sulfide solid electrolyte and the electrode active material. That is, the method for manufacturing the electrode composite material of this embodiment may use other components such as a conductive material and a binder in addition to the modified sulfide solid electrolyte and the electrode active material. Other components such as a conductive material and a binder may be further added to the modified sulfide solid electrolyte and the electrode active material in the mixing of the modified sulfide solid electrolyte and the electrode active material and mixed for use.

[0446] As conductive materials, from the viewpoint of improving battery performance by improving electron conductivity, examples include artificial graphite, graphite carbon fiber, resin-fired carbon, pyrolysis vapor-grown carbon, coke, mesophase carbon microbeads, furfuryl alcohol resin-fired carbon, polyphenylene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and carbon materials that are difficult to graphitize.

[0447] By using a binder, the strength of the positive electrode and the negative electrode can be improved.

[0448] There are no particular restrictions on the binder as long as it can impart functions such as adhesion and flexibility. Examples include fluorine-based polymers such as polytetrafluoroethylene and polyvinylidene fluoride, thermoplastic elastomers such as butene rubber and styrene-butadiene rubber, acrylic resins, acrylic polyol resins, polyvinyl acetal resins, polyvinyl butyral resins, silicone resins and other resins.

[0449] The blending ratio (mass ratio) of the electrode active material and the modified sulfide solid electrolyte in the electrode composite material is preferably 99.5:0.5 to 40:60, more preferably 99:1 to 50:50, and even more preferably 98:2 to 60:40 in consideration of improvement in battery performance and manufacturing efficiency.

[0450] When containing a conductive material, the content of the conductive material in the electrode composite material is not particularly limited. If the battery performance is improved and the manufacturing efficiency is taken into consideration, it is preferably 0.5 mass % or more, more preferably 1 mass % or more, and further preferably 1.5 mass % or more. As an upper limit, it is preferably 10 mass % or less, preferably 8 mass % or less, and further preferably 5 mass % or less.

[0451] In addition, when containing a binder, the content of the binder in the electrode composite material is not particularly limited. If the battery performance is improved and the manufacturing efficiency is taken into consideration, it is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more. As an upper limit, it is preferably 20% by mass or less, preferably 15% by mass or less, and further preferably 10% by mass or less.

[0452] 〔Lithium-ion battery〕

[0453] The lithium ion battery of the present embodiment includes at least one selected from the modified sulfide solid electrolyte and the electrode composite material of the present embodiment described above, or includes at least one selected from the modified sulfide solid electrolyte and the electrode composite material of the other embodiment described above.

[0454] The lithium ion battery of the present embodiment is not particularly limited in its structure as long as it includes the modified sulfide solid electrolyte of the present embodiment described above, an electrode composite material containing the modified sulfide solid electrolyte, or any one of the modified sulfide solid electrolyte of another embodiment and an electrode composite material containing the modified sulfide solid electrolyte of another embodiment, and has the structure of a general lithium ion battery.

[0455] As the lithium ion battery of the present embodiment, for example, a lithium ion battery having a positive electrode layer, a negative electrode layer, an electrolyte layer and a current collector is preferred. As the positive electrode layer and the negative electrode layer, the positive electrode layer and the negative electrode layer of the electrode composite material of the present embodiment are preferably used, and as the electrolyte layer, the modified sulfide solid electrolyte of the present embodiment or the modified sulfide solid electrolyte of another embodiment is preferably used.

[0456] As the current collector, any known current collector may be used. For example, a layer obtained by coating a substance that reacts with the above-mentioned solid electrolyte, such as Au, Pt, Al, Ti, or Cu, with Au or the like can be used.

[0457] Example

[0458] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples at all.

[0459] Production Example: Preparation of Sulfide Solid Electrolyte

[0460] In a Schlenk bottle (capacity: 100 mL) with a stirrer, 0.59 g of lithium sulfide, 0.95 g of phosphorus pentasulfide, 0.19 g of lithium bromide, and 0.28 g of lithium iodide were introduced under a nitrogen atmosphere. After the stirrer was rotated, 20 mL of tetramethylethylenediamine (TMEDA) as a complexing agent was added, and stirring was continued for 12 hours. The obtained complex-containing material was dried under vacuum (room temperature: 23° C.) to obtain a powdered complex. Next, the powder of the complex was heated at 120° C. for 2 hours under vacuum to obtain an amorphous sulfide solid electrolyte. Furthermore, the amorphous sulfide solid electrolyte was heated at 140° C. for 2 hours under vacuum to obtain a crystalline sulfide solid electrolyte (the heating temperature (140° C. in this case) used to obtain a crystalline sulfide solid electrolyte is sometimes referred to as the "crystallization temperature").

[0461] The BET specific surface areas of the amorphous sulfide solid electrolyte and the crystalline sulfide solid electrolyte were measured to be 40 m 2 / g.

[0462] Example 1

[0463] In a nitrogen atmosphere, 3 g of the crystalline sulfide solid electrolyte obtained in the above-mentioned manufacturing example was weighed and added to a Schlenk bottle (capacity: 100 mL) equipped with a stirrer, and 22 g of toluene was added and stirred to prepare a slurry-like fluid. To the slurry-like fluid, 0.3 g (a content of 10 parts by mass, which is 10% by mass relative to 100 parts by mass of the crystalline sulfide solid electrolyte) of heptaldehyde as a compound (1) having a formyl group (CH(=O)-) (compound 1, in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 After stirring for 10 minutes, toluene was distilled off by vacuum drying to obtain a modified sulfide solid electrolyte.

[0464] The oil absorption and ion conductivity of the obtained modified sulfide solid electrolyte were measured by the following method. The reduction rate of the oil absorption was calculated by the following method. The measurement results and calculation results are shown in Table 1.

[0465] Embodiments 2 to 22

[0466] A modified sulfide solid electrolyte was prepared in the same manner as in Example 1, except that the types of the compounds were changed to Compounds 2 to 19 and 23 to 25 shown in Table 1.

[0467] The oil absorption and ion conductivity of the obtained modified sulfide solid electrolyte were measured by the following method. The reduction rate of the oil absorption was calculated by the following method. The measurement results and calculation results are shown in Table 1.

[0468] Comparative Examples 1 to 3

[0469] A modified sulfide solid electrolyte was prepared in the same manner as in Example 1, except that the types of the compounds were changed to Compounds 20 to 22 shown in Table 1.

[0470] The oil absorption and ion conductivity of the obtained modified sulfide solid electrolyte were measured by the following method. The reduction rate of the oil absorption was calculated by the following method. The measurement results and calculation results are shown in Table 1.

[0471] Comparative Example 4

[0472] The oil absorption and ion conductivity of the sulfide solid electrolyte obtained in the above production example were measured by the following method. The reduction rate of the oil absorption was calculated by the following method. The measurement results and calculation results are shown in Table 1. The oil absorption of the sulfide solid electrolyte was 1.03 mL / g.

[0473] (Measurement of specific surface area)

[0474] The specific surface area was measured by the BET method based on krypton (Kr) adsorption using a gas adsorption amount measuring device.

[0475] (Measurement of oil absorption)

[0476] 1 g of the solid electrolyte obtained in the examples and comparative examples was used as a sample. One drop of butyl butyrate was added using a dropper in an agate mortar and then stirred with a spatula. This operation was repeated until the sample became a paste. The total amount of butyl butyrate added was defined as the oil absorption (mL / g).

[0477] (Reduction rate of oil absorption)

[0478] The oil absorption of the sulfide solid electrolyte obtained in the manufacturing example was measured in the same manner as in the above (Measurement of Oil Absorption). The oil absorption A of the sulfide solid electrolyte and the oil absorption B of the sulfide solid electrolyte obtained in the examples and comparative examples based on the above (Measurement of Oil Absorption) were used to calculate by the following formula, and the calculated value was taken as the reduction rate of the oil absorption.

[0479] Oil absorption reduction rate = (oil absorption A - oil absorption B) / oil absorption A × 100 (%)

[0480] (Measurement of ionic conductivity)

[0481] In this example, the measurement of ion conductivity was performed as follows.

[0482] The sulfide solid electrolyte is formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm are used to make a sample. The top and bottom of the sample are taken as electrode terminals, and the AC impedance method is used for measurement at 25°C (frequency range: 1 MHz to 100 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.

[0483] R=ρ(L / S)

[0484] σ=1 / ρ

[0485] [Table 1]

[0486] Table 1

[0487]

[0488] The details of the compounds shown in Table 1 are as follows.

[0489] Compound 1 (belonging to compound (1)): Heptanal, in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 The structural formula is as follows.

[0490] [Chemistry 15]

[0491]

[0492] Compound 2 (belonging to compound (1)): undecanal, in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 It is decyl. The structural formula is as follows.

[0493] [Chemistry 16]

[0494]

[0495] Compound 3 (belongs to compound (1)): benzyloxyacetaldehyde. In the general formula (1), X 11 is an oxygen atom, R 11 is methylene, n 11 is 0, R 12 is benzyl. The structural formula is as follows.

[0496] [Chemistry 17]

[0497]

[0498] Compound 4 (belongs to compound (2)): acetylacetone. In the general formula (2), R 21 and X 21 is a single bond, R 22 The structural formula is as follows.

[0499] [Chemistry 18]

[0500]

[0501] Compound 5 (belongs to compound (3)): 1,3-dibromopropane. In the general formula (3), R 31 is methylene, X 31and X 32 is a bromine atom. The structural formula is as follows.

[0502] [Chemistry 19]

[0503]

[0504] Compound 6 (belongs to compound (3)): 1,4-dibromobutane. In the general formula (3), R 31 is methylene, X 31 and X 32 is a bromine atom. The structural formula is as follows.

[0505] [Chemistry 20]

[0506]

[0507] Compound 7 (belongs to compound (3)): 1,6-dibromohexane. In the general formula (3), R 31 is 1,4-butanediyl, X 31 and X 32 is a bromine atom. The structural formula is as follows.

[0508] [Chemistry 21]

[0509]

[0510] Compound 8 (belongs to compound (3)): 1,10-dibromodecane. In the general formula (3), R 31 is 1,8-octanediyl, X 31 and X 32 is a bromine atom. The structural formula is as follows.

[0511] [Chemistry 22]

[0512]

[0513] Compound 9 (belonging to compound (4)): 1-dodecanethiol. In the general formula (4-1), R 411 is a single bond, n 411 is 0, R 413 is 1,12-dodecanediyl, X 411 is a hydrogen atom. The structural formula is as follows.

[0514] [Chemistry 23]

[0515]

[0516] Compound 10 (belonging to compound (4)): 1,10-decanedithiol. In the general formula (4-1), R 411 is a single bond, n 411 is 0, R 413is 1,10-decanediyl, X 411 It is a thiol group. The structural formula is as follows.

[0517] [Chemistry 24]

[0518]

[0519] Compound 11 (belonging to compound (4)): 3-mercaptopropyltrimethoxysilane. In the general formula (4-2), R 421 is 1,3-propanediyl, R 423 Methyl, n 421 is 0, n 422 The structural formula is as follows.

[0520] [Chemistry 25]

[0521]

[0522] Compound 12 (belonging to compound (5)): tri-n-octylphosphine oxide. In the general formula (5-1), R 511 , R 512 and R 513 It is 1-octyl. Its structural formula is as follows.

[0523] [Chemistry 26]

[0524]

[0525] Compound 13 (belonging to compound (5)): tri-n-octylphosphine. In the general formula (5-2), R 521 , R 522 and R 523 It is 1-octyl. Its structural formula is as follows.

[0526] [Chemistry 27]

[0527]

[0528] Compound 14 (belongs to compound (5)): triphenylphosphine. In the general formula (5-2), R 521 , R 522 and R 523 It is phenyl. The structural formula is as follows.

[0529] [Chemistry 28]

[0530]

[0531] Compound 15 (belonging to compound (5)): 1,4-bis(diphenylphosphino)butane. In the general formula (5-3), R 531 , R 532 , R 535 and R 536is phenyl, R 533 is 1,4-butanediyl, R 534 and X 531 is a single bond. The structural formula is as follows.

[0532] [Chemistry 29]

[0533]

[0534] Compound 16 (belonging to compound (5)): bis[(2-diphenylphosphino)phenyl]ether. In the general formula (5-3), R 531 , R 532 , R 535 and R 536 is phenyl, R 533 and R 534 is phenylenediyl, X 531 is an oxygen atom. The structural formula is as follows.

[0535] [Chemistry 30]

[0536]

[0537] Compound 17 (belonging to compound (5)): 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene. In the general formula (5-3), R 531 , R 532 , R 535 and R 536 is phenyl, R 533 is xanthene-4,5-diyl, R 534 and X 531 is a single bond. The structural formula is as follows.

[0538] [Chemistry 31]

[0539]

[0540] Compound 18: tri-n-octyl borate. In the general formula (6), R 61 , R 62 and R 63 It is octyloxy. The structural formula is as follows.

[0541] [Chemistry 32]

[0542]

[0543] Compound 19: tri-n-octadecyl borate. In the general formula (6), R 61 , R 62 and R 63 is octadecyloxy. The structural formula is as follows.

[0544] [Chemistry 33]

[0545]

[0546] Compound 20: dimethyl oxalate. The structural formula is as follows.

[0547] [Chemistry 34]

[0548]

[0549] Compound 21: 1,2-dimethoxyethane. The structural formula is as follows.

[0550] [Chemistry 35]

[0551]

[0552] Compound 22: diethylene glycol dimethyl ether. The structural formula is as follows.

[0553] [Chemistry 36]

[0554]

[0555] Compound 23 (belonging to compound (1)): 2-[(tert-butyldimethylsilyl)oxy]acetaldehyde. In the general formula (1), R 11 is methyl, R 12 is tert-butyl (1,1-dimethylethyl), X 11 is a group represented by the general formula (1a), wherein R 11a and R 12a Methyl, n 11 is 0. The structural formula is as follows.

[0556] [Chemistry 37]

[0557]

[0558] Compound 24 (belonging to compound (1)): hexanal, in the general formula (1), R 11 and X 11 is a single bond, n 11 is 0, R 12 The structural formula is as follows.

[0559] [Chemistry 38]

[0560]

[0561] Compound 25 (belonging to compound (2)): benzyloxyacetone (molecular weight: 164.20). In the general formula (2), X 21 is an oxygen atom, R 21 is methylene, R 22 is benzyl, n 21is 0. The structural formula is as follows.

[0562] [Chemistry 39]

[0563]

[0564] According to the examples, it was confirmed that the oil absorption of the modified sulfide solid electrolyte of the present embodiment was 1.10 mL / g or less and the reduction rate of the oil absorption was 13% or more. Therefore, even if the specific surface area was large and 10 m 2 / g or more, but it is still a modified sulfide solid electrolyte with a small oil absorption and excellent coating adaptability. In addition, it is also confirmed that the ion conductivity is 0.80mS / cm or more. It can be seen that by containing compounds (1) to (6), the surface is coated, so that the ion conductivity shows a tendency to decrease, but the tendency to decrease is suppressed as much as possible, and even if the specific surface area is as large as 10m 2 / g or more, and also has excellent properties such as small oil absorption and excellent coating adaptability.

[0565] On the other hand, the sulfide solid electrolyte of Comparative Example 4 which was not mixed with the above-mentioned compounds (1) to (6) and did not contain these compounds was the sulfide solid electrolyte prepared in the Production Example and was a conventional sulfide solid electrolyte itself. It was confirmed that the specific surface area of ​​Comparative Example 4 was 40 m 2 The oil absorption of the sulfide solid electrolyte of 0.99 mL / g was high, and the coating suitability was poor. In addition, in Comparative Examples 1 to 3 using compounds other than Compounds (1) to (6), the oil absorption was as high as 1.1 to 1.2 mL / g, and the effect of reducing the oil absorption corresponding to the reduction in ionic conductivity was not observed.

[0566] From the above results, it was confirmed that in the method for producing a modified sulfide solid electrolyte of the present embodiment, the specific surface area of ​​the modified sulfide solid electrolyte is relatively large, and the specific surface area of ​​the modified sulfide solid electrolyte is relatively large. 2 A sulfide solid electrolyte with a carbonyl content of 0.1 / g or more is preferred because it can exhibit effects of reducing oil absorption and improving coating suitability.

[0567] Industrial Applicability

[0568] The modified sulfide solid electrolyte of the present embodiment has excellent coating adaptability when applied as a paste even if it is a sulfide solid electrolyte with a large specific surface area, and can effectively demonstrate excellent battery performance. In addition, the modified sulfide solid electrolyte of the present embodiment has high ion conductivity and is therefore suitable for use in batteries, particularly batteries used in information-related devices or communication devices such as personal computers, video cameras, and mobile phones.

Claims

1. A modified sulfide solid electrolyte, characterized in that: Contains: Sulfide solid electrolyte with a BET surface area of ​​10m 2 / g or more and containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms; at least one compound selected from the following compounds (1) to (6), Compound (1) a compound having a formyl group (CH(=O)-); Compound (2) a compound having one or more acetyl groups (CH3C(=O)-); Compound (3) a compound having two or more halogen-containing groups and organic groups represented by -CH2X, wherein X represents a fluorine atom or a bromine atom; Compound (4) a thiol compound; Compound (5) a metal-free phosphorus compound, wherein the compound does not contain an oxygen atom singly bonded to a phosphorus atom; Compound (6) is a boron compound containing no metal.

2. The modified sulfide solid electrolyte according to claim 1, characterized in that The compound (1) is a compound represented by the following general formula (1): [Chemistry 1] In the general formula (1), R 11 and R 12 Each independently represents an organic group or a single bond, X 11 represents an oxygen atom, a sulfur atom, a group represented by the general formula (1a) or a single bond, n 11 represents 0 or 1. In the general formula (1a), R 11a and R 12a Each independently represents an organic group.

3. The modified sulfide solid electrolyte according to claim 1 or 2, characterized in that: The compound (2) is a compound represented by the following general formula (2): [Chemistry 2] In the general formula (2), R 21 and R 22 Each independently represents an organic group or a single bond, X 21 represents an oxygen atom, a sulfur atom or a single bond, n 21 Represents 0 or 1.

4. The modified sulfide solid electrolyte according to any one of claims 1 to 3, characterized in that The compound (3) is a compound represented by the following general formula (3): [Chemistry 3] In the general formula (3), R 31 represents an organic group or a single bond, X 31 and X 32 Each independently represents a fluorine atom or a bromine atom.

5. The modified sulfide solid electrolyte according to any one of claims 1 to 4, characterized in that The compound (4) is at least one compound selected from the compounds represented by the following general formula (4-1) and the compounds represented by the following general formula (4-2), [Chemistry 4] In the general formula (4-1), R 411 , R 412 and R 413 Each independently represents an organic group or a single bond, X 411 represents a hydrogen atom or a thiol group, n 411 represents an integer from 0 to 3, where R 411 , R 412 and R 413 At least one of is an organic group, In the general formula (4-2), R 421 , R 422 and R 423 Each independently represents an organic group, n 421 、n 422 Integer from 0 to 3, n 421 and n 422 Satisfy n 421 +n 422 =3.

6. The modified sulfide solid electrolyte according to any one of claims 1 to 5, characterized in that The compound (5) is at least one compound selected from the group consisting of a compound represented by the following general formula (5-1), a compound represented by the following general formula (5-2), and a compound represented by the following general formula (5-3). [Chemistry 5] In the general formula (5-1), R 511 , R 512 and R 513 Each independently represents an organic group. In the general formula (5-2), R 521 , R 522 and R 523 Each independently represents an organic group. In the general formula (5-3), R 531 , R 532 , R 535 and R 536 Each independently represents an organic group, R 533 and R 534 Each independently represents a single bond or an organic group, X 531 represents a single bond or an oxygen atom. In addition, R 533 and R 534 At least one of R is an organic group, 533 With R 534 They may be bonded to each other to form a condensed ring.

7. The modified sulfide solid electrolyte according to any one of claims 1 to 6, characterized in that The molecular weight of the compound (5) is 3,000 or less.

8. The modified sulfide solid electrolyte according to any one of claims 1 to 7, characterized in that The compound (6) is a compound represented by the following general formula (6): [Chemistry 6] In the general formula (6), R 61 , R 62 and R 63 Each independently represents an organic group.

9. The modified sulfide solid electrolyte according to any one of claims 1 to 8, characterized in that The content of the compound is 0.03 parts by mass or more and 25 parts by mass or less relative to 100 parts by mass of the sulfide solid electrolyte.

10. A method for producing a modified sulfide solid electrolyte, characterized in that: include: The BET specific surface area is 10m 2 / g or more sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, at least one compound selected from the following compounds (1) to (6) and an organic solvent; as well as removing the organic solvent, Compound (1) a compound having a formyl group (CH(=O)-); Compound (2) a compound having one or more acetyl groups (CH3C(=O)-); Compound (3) a compound having two or more halogen-containing groups and organic groups represented by -CH2X, wherein X represents a fluorine atom, a chlorine atom, a bromine atom or an iodine atom; Compound (4) a thiol compound; Compound (5) a metal-free phosphorus compound; Compound (6) is a boron compound containing no metal.

11. The method for producing a modified sulfide solid electrolyte according to claim 10, wherein: The organic solvent is at least one solvent selected from aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, ether solvents, ester solvents, and nitrile solvents.

12. An electrode composite material, characterized in that: A modified sulfide solid electrolyte comprising the modified sulfide solid electrolyte according to any one of claims 1 to 9 and an electrode active material.

13. A lithium ion battery, characterized in that: A method comprising at least one of the modified sulfide solid electrolyte according to any one of claims 1 to 9 and the electrode composite material according to claim 12.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Solid electrolyte composition, sheet for all-solid type secondary battery, all-solid type secondary battery, and methods for manufacturing sheet for all-solid type secondary battery and all-solid type secondary battery

    JP2017147173A

  • Solid electrolyte composition, all-solid type secondary battery sheet arranged by use thereof, all-solid type secondary battery, and manufacturing methods thereof

    JP2017157300A

  • All-solid type secondary battery, solid electrolyte-containing sheet and solid electrolyte composition

    JP2019067523A

  • Method for producing composite solid electrolyte

    JP2020087633A